Uncovering correlates of decline and critical refuges for a threatened terrestrial mammal - Natalya M. Maitz; Michelle S. Ward; Jonathan R. Rhodes; Ben C. Scheele; Hugh P. Possingham; Diana O. Fisher (Conservation Biology, 2026)
Globally, the geographic ranges of numerous species are contracting. Identifying spatiotemporal patterns of threat impact can illuminate why species decline in some parts of their range but persist in others. We developed a correlative approach to identify species’ response thresholds and locate ecological refuge areas associated with persistence to inform conservation planning and management. We integrated changes in realized niche characteristics for a threatened Australian mammal, the brush‐tailed rock‐wallaby ( Petrogale penicillata ), with the distributions of threatening processes and environmental features to identify predictors of extirpation and persistence. We used occurrence records to construct historical (2004 or before) and contemporary (2005–2022) species distribution models. We then determined differences in niche characteristics between areas of extirpation and persistence. We applied generalized additive mixed models to determine species‐specific thresholds for extirpation, which we used to identify ecological refuges. Across the two periods, brush‐tailed rock‐wallaby habitat declined by 75%, resulting in realized niche shifts. Extirpations occurred where habitat distance to water increased, and red fox ( Vulpes vulpes ) densities and feral goat ( Capra hircus ) habitat suitability were relatively high. Relatively high topographic ruggedness and high minimum temperatures were associated with persistence. Species persistence was also positively correlated with increasing dingo ( Canis familiaris ) habitat suitability, and inappropriate fire regimes (e.g., more frequent fires than expected for a vegetation group), both of which have been suggested as threats to the species. Specific refuge locations were identified in southeastern Queensland and northern New South Wales. Our findings highlight the importance of quantitative species‐specific threat assessments to prevent misguided conclusions from cross‐taxa threat generalizations. As spatial data become increasingly accessible, our novel approach will provide practitioners with evidence on which to base fine‐scale investigations. Our approach can be applied to other species undergoing range contractions.

Structured decision‐making as a framework to incorporate social equity into conservation decisions - Emily Massingham; Angela J. Dean; Hugh P. Possingham (Conservation Biology, 2026)
Many conservation challenges require negotiating trade‐offs between the needs of different actors. Global frameworks such as the Kunming–Montreal Global Biodiversity Framework explicitly call for diverse participation and social equity in conservation decision‐making. Achieving this requires integrating equity into both decisions and decision‐making processes. Despite shifts toward strengthening social equity, practical guidance for incorporating equity into conservation decision‐making processes remains limited. We argue that structured decision‐making (SDM), an organized approach designed for complex decisions involving diverse actors, provides a useful framework for considering equity in conservation decision‐making. We developed 10 strategies for improving social equity in conservation decision‐making to strengthen both social and conservation outcomes. We systematically integrated equity's multiple dimensions throughout every SDM stage, making equity an inherent element in decision‐making rather than an afterthought. For example, when clarifying the decision context, practitioners can create thorough stakeholder maps, ask diverse social groups how they want to be engaged, and design processes to facilitate their participation. At later stages, when assessing links between actions and outcomes, structured methods for information aggregation and tools to enable shared understanding support development of a shared vision and a path forward. By transforming general calls for inclusivity into specific, actionable strategies, we provide conservation practitioners, researchers, and decision makers practical guidance bridging the theory‐to‐practice gap.

Selecting Suitable Nitrogen Offset Strategies In Tropical And Subtropical Regions Globally With Implications To The Great Barrier Reef, Australia - Diego F. Correa; Ryan D. R. Turner; Martine Maron; Lina M. González-González; Michele A. Burford; Jing Lu; Joanne Burton; Joseph McMahon; Debra Chamberlain; Yongjing Mao; Hugh Possingham; Michael St. J. Warne (Environmental Management, 2026)
Water pollution from agricultural, industrial, and urban activities threatens aquatic ecosystems and the essential services they provide. Excess nitrogen has been identified as a key driver of water quality degradation, impacting biodiversity, food security, and human health. One approach to mitigating nitrogen pollution is water quality offsetting, compensating for pollution impacts by implementing nitrogen reduction measures elsewhere to achieve no net decline in water quality. Selecting and implementing suitable nitrogen offset types remains challenging. This study presents a framework for identifying, selecting, and implementing effective nitrogen offset strategies in tropical and subtropical regions globally, using the Great Barrier Reef Catchment Area (GBRCA) as an example. This framework is based on the premise that effective nitrogen offset design requires integrating evidence on nitrogen mitigation performance, appropriate criteria for selecting offset types, and adaptive management to address uncertainty in environmental outcomes. Accordingly, the framework comprises three interrelated components: (1) assessment of water quality improvement methods for nitrogen reduction in the GBRCA and other tropical and subtropical regions based on performance (i.e., efficacy, effectiveness, and efficiency); (2) selection of suitable offset types based on their performance, co-benefits, and spatial and technical feasibility; and (3) integration of adaptive management strategies, Geographic Information Systems (GIS) tools, and monitoring systems to strengthen the effectiveness of nitrogen offsetting. This is the first global assessment of nitrogen offset performance in tropical and subtropical regions, offering insights to improve water quality management through offsetting. This framework is adaptable to other regions and pollutants, guiding effective offset implementation to enhance watershed resilience.

A framework for designing multi-objective landscapes for conservation - Alienor L.M. Chauvenet; Anna R. Renwick; Hugh P. Possingham; Vanessa M. Adams; Jennifer McGowan; Vesna Gagić; Nancy A. Schellhorn (Biological Conservation, 2026)

Multiple-use spatial planning for sustainable development and conservation - Sandra Neubert; Jennifer McGowan; Kristian Metcalfe; Jeffrey O. Hanson; Kristine Camille V. Buenafe; Alvise Dabalà; Daniel C. Dunn; Jason D. Everett; Hugh P. Possingham; Vanessa Stelzenmüller; Andy Estep; Jamison Ervin; et al. (Trends in Ecology & Evolution, 2025)

Expand or better manage protected areas: A framework for minimizing extinction risk when threats are concentrated near edges - Brendan G. Dillon; Hugh P. Possingham; Matthew H. Holden (Biological Conservation, 2025)

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Advances in systematic conservation planning to meet global biodiversity goals - Sylvaine Giakoumi; Anthony J. Richardson; Aggeliki Doxa; Stefano Moro; Marco Andrello; Jeffrey O. Hanson; Virgilio Hermoso; Tessa Mazor; Jennifer McGowan; Heini Kujala; Elizabeth Law; Jorge G. Álvarez-Romero; et al. (Trends in Ecology & Evolution, 2025)

Systematic conservation prioritization with the prioritizr R package - Jeffrey O. Hanson; Richard Schuster; Matthew Strimas‐Mackey; Nina Morrell; Brandon P. M. Edwards; Peter Arcese; Joseph R. Bennett; Hugh P. Possingham (Conservation Biology, 2025)
Plans for expanding protected area systems (prioritizations) need to fulfill conservation objectives. They also need to account for other factors, such as economic feasibility and anthropogenic land‐use requirements. Although prioritizations are often generated with decision support tools, most tools have limitations that hinder their use for decision‐making. We outlined how the prioritizr R package ( https://prioritizr.net ) can be used for systematic conservation prioritization. This decision support tool provides a flexible interface to build conservation planning problems. It can leverage a variety of commercial (e.g., Gurobi) and open‐source (e.g., CBC and SYMPHONY) exact algorithm solvers to identify optimal solutions in a short period. It is also compatible with a variety of spatially explicit (e.g., ESRI Shapefile, GeoTIFF) and nonspatial tabular (e.g., Microsoft Excel Spreadsheet) data formats. Additionally, it provides functionality for evaluating prioritizations, such as assessing the relative importance of different places selected by a prioritization. To showcase the prioritizr R package, we applied it to a case study based in Washington state (United States) for which we developed a prioritization to improve protected area coverage of native avifauna. We accounted for land acquisition costs, existing protected areas, places that might not be suitable for protected area establishment, and spatial fragmentation. We also conducted a benchmark analysis to examine the performance of different solvers. The prioritization identified 12,400 km 2 of priority areas for increasing the percentage of species’ distributions covered by protected areas. Although open source and commercial solvers were able to quickly solve large‐scale conservation planning problems, commercial solvers were required for complex, large‐scale problems.. The prioritizr R package is available on the Comprehensive R Archive Network (CRAN). In addition to reserve selection, it can inform habitat restoration, connectivity enhancement, and ecosystem service provisioning. It has been used in numerous conservation planning exercises to inform best practices and aid real‐world decision‐making.

Conservation planning for retention, not just protection - Pablo Jose Negret; Ruben Venegas; Laura J. Sonter; Hugh P. Possingham; Martine Maron (Global Change Biology, 2024)
Most protected area (PA) planning aims to improve biota representation within the PA system, but this does not necessarily achieve the best outcomes for biota retention across regions when we also consider habitat loss in areas outside the PA system. Here, we assess the implications that different PA expansion strategies can have on the retention of species habitat across an entire region. Using retention of forest habitat for Colombia's 550 forest‐dependent bird species as our outcome variable, we found that when a minimum of 30% of each species' habitat was included in the PA system, a pattern of PA expansion targeting areas at highest deforestation risk (risk‐prevention) led to the retention, on average, of 7.2% more forest habitat per species by 2050 than did a pattern that targeted areas at lowest risk (risk‐avoidance). The risk‐prevention approach cost more per km 2 of land conserved, but it was more cost‐effective in retaining habitat in the landscape (50%–69% lower cost per km 2 of avoided deforestation). To have the same effectiveness preventing habitat loss in Colombia, the risk‐avoidance approach would require more than twice as much protected area, costing three times more in the process. Protected area expansion should focus on the contributions of PAs to outcomes not only within PA systems themselves, but across entire regions.

Public opinion on protecting iconic species depends on individual wellbeing: Perceptions about orangutan conservation in Indonesia and Malaysia - Emily J. Massingham; Kerrie A. Wilson; Erik Meijaard; Marc Ancrenaz; Truly Santika; Rachel Friedman; Hugh P. Possingham; Angela J. Dean (Environmental Science & Policy, 2023)

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Protected area planning to conserve biodiversity in an uncertain future - Richard Schuster; Rachel Buxton; Jeffrey O. Hanson; Allison D. Binley; Jeremy Pittman; Vivitskaia Tulloch; Frank A. La Sorte; Patrick R. Roehrdanz; Peter H. Verburg; Amanda D. Rodewald; Scott Wilson; Hugh P. Possingham; et al. (Conservation Biology, 2023)
Protected areas are a key instrument for conservation. Despite this, they are vulnerable to risks associated with weak governance, land‐use intensification, and climate change. We used a novel hierarchical optimization approach to identify priority areas for expanding the global protected area system that explicitly accounted for such risks while maximizing protection of all known terrestrial vertebrate species. To incorporate risk categories, we built on the minimum set problem, where the objective is to reach species distribution protection targets while accounting for 1 constraint, such as land cost or area. We expanded this approach to include multiple objectives accounting for risk in the problem formulation by treating each risk layer as a separate objective in the problem formulation. Reducing exposure to these risks required expanding the area of the global protected area system by 1.6% while still meeting conservation targets. Incorporating risks from weak governance drove the greatest changes in spatial priorities for protection, and incorporating risks from climate change required the largest increase (2.52%) in global protected area. Conserving wide‐ranging species required countries with relatively strong governance to protect more land when they bordered nations with comparatively weak governance. Our results underscore the need for cross‐jurisdictional coordination and demonstrate how risk can be efficiently incorporated into conservation planning. Planeación de las áreas protegidas para conservar la biodiversidad en un futuro incierto

Effects of different management strategies on long‐term trends of Australian threatened and near‐threatened mammals - Ayesha I. T. Tulloch; Micha V. Jackson; Elisa Bayraktarov; Alexander R. Carey; Diego F. Correa‐Gomez; Michael Driessen; Ian C. Gynther; Mel Hardie; Katherine Moseby; Liana Joseph; Harriet Preece; Andrés Felipe Suarez‐Castro; et al. (Conservation Biology, 2023)
Monitoring is critical to assess management effectiveness, but broadscale systematic assessments of monitoring to evaluate and improve recovery efforts are lacking. We compiled 1808 time series from 71 threatened and near‐threatened terrestrial and volant mammal species and subspecies in Australia (48% of all threatened mammal taxa) to compare relative trends of populations subject to different management strategies. We adapted the Living Planet Index to develop the Threatened Species Index for Australian Mammals and track aggregate trends for all sampled threatened mammal populations and for small ( 5500 g) from 2000 to 2017. Unmanaged populations (42 taxa) declined by 63% on average; unmanaged small mammals exhibited the greatest declines (96%). Populations of 17 taxa in havens (islands and fenced areas that excluded or eliminated introduced red foxes [ Vulpes vulpes ] and domestic cats [ Felis catus ]) increased by 680%. Outside havens, populations undergoing sustained predator baiting initially declined by 75% but subsequently increased to 47% of their abundance in 2000. At sites where predators were not excluded or baited but other actions (e.g., fire management, introduced herbivore control) occurred, populations of small and medium mammals declined faster, but large mammals declined more slowly, than unmanaged populations. Only 13% of taxa had data for both unmanaged and managed populations; index comparisons for this subset showed that taxa with populations increasing inside havens declined outside havens but taxa with populations subject to predator baiting outside havens declined more slowly than populations with no management and then increased, whereas unmanaged populations continued to decline. More comprehensive and improved monitoring (particularly encompassing poorly represented management actions and taxonomic groups like bats and small mammals) is required to understand whether and where management has worked. Improved implementation of management for threats other than predation is critical to recover Australia's threatened mammals.

How to prioritize species recovery after a megafire - Michelle Ward; Josie Carwardine; James E. M. Watson; Anna Pintor; Stephanie Stuart; Hugh P. Possingham; Jonathan R. Rhodes; Alexander R. Carey; Nancy Auerbach; April Reside; Chuan Ji Yong; Ayesha I. T. Tulloch (Conservation Biology, 2022)
Due to climate change, megafires are increasingly common and have sudden, extensive impacts on many species over vast areas, leaving decision makers uncertain about how best to prioritize recovery. We devised a decision‐support framework to prioritize conservation actions to improve species outcomes immediately after a megafire. Complementary locations are selected to extend recovery actions across all fire‐affected species’ habitats. We applied our method to areas burned in the 2019−2020 Australian megafires and assessed its conservation advantages by comparing our results with outcomes of a site‐richness approach (i.e., identifying areas that cost‐effectively recover the most species in any one location). We found that 290 threatened species were likely severely affected and will require immediate conservation action to prevent population declines and possible extirpation. We identified 179 subregions, mostly in southeastern Australia, that are key locations to extend actions that benefit multiple species. Cost savings were over AU$300 million to reduce 95% of threats across all species. Our complementarity‐based prioritization also spread postfire management actions across a wider proportion of the study area compared with the site‐richness method (43% vs. 37% of the landscape managed, respectively) and put more of each species’ range under management (average 90% vs. 79% of every species’ habitat managed). In addition to wildfire response, our framework can be used to prioritize conservation actions that will best mitigate threats affecting species following other extreme environmental events (e.g., floods and drought).

Wilderness forms and their implications for global environmental policy and conservation - Katharina‐Victoria Pérez‐Hämmerle; Katie Moon; Rubén Venegas‐Li; Sean Maxwell; Jeremy S. Simmonds; Oscar Venter; Stephen T. Garnett; Hugh P. Possingham; James E. M. Watson (Conservation Biology, 2022)
With the intention of securing industry‐free land and seascapes, protecting wilderness entered international policy as a formal target for the first time in the zero draft of the Post‐2020 Global Biodiversity Framework under the Convention on Biological Diversity. Given this increased prominence in international policy, it is timely to consider the extent to which the construct of wilderness supports global conservation objectives. We evaluated the construct by overlaying recently updated cumulative human pressure maps that offer a global‐scale delineation of industry‐free land as wilderness with maps of carbon stock, species richness, and ground travel time from urban centers. Wilderness areas took variable forms in relation to carbon stock, species richness, and proximity to urban centers, where 10% of wilderness areas represented high carbon and species richness, 20% low carbon and species richness, and 3% high levels of remoteness (>48 h), carbon, and species richness. Approximately 35% of all remaining wilderness in 2013 was accessible in

Communicating the true challenges of saving species: response to Wiedenfeld et al. - James E. M. Watson; Jeremy S. Simmonds; Michelle Ward; Chuan J. Yong; April E. Reside; Hugh P. Possingham; Andrew Rogers; Josie Carwardine (Conservation Biology, 2022)

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Decision-making with ecological process for coastal and marine planning: current literature and future directions - Debbie A. Chamberlain; Hugh P. Possingham; Stuart R. Phinn (Aquatic Ecology, 2022)

An introduction to decision science for conservation - Victoria Hemming; Abbey E. Camaclang; Megan S. Adams; Mark Burgman; Katherine Carbeck; Josie Carwardine; Iadine Chadès; Lia Chalifour; Sarah J. Converse; Lindsay N. K. Davidson; Georgia E. Garrard; Riley Finn; et al. (Conservation Biology, 2022)
Biodiversity conservation decisions are difficult, especially when they involve differing values, complex multidimensional objectives, scarce resources, urgency, and considerable uncertainty. Decision science embodies a theory about how to make difficult decisions and an extensive array of frameworks and tools that make that theory practical. We sought to improve conceptual clarity and practical application of decision science to help decision makers apply decision science to conservation problems. We addressed barriers to the uptake of decision science, including a lack of training and awareness of decision science; confusion over common terminology and which tools and frameworks to apply; and the mistaken impression that applying decision science must be time consuming, expensive, and complex. To aid in navigating the extensive and disparate decision science literature, we clarify meaning of common terms: decision science , decision theory , decision analysis , structured decision‐making , and decision‐support tools . Applying decision science does not have to be complex or time consuming; rather, it begins with knowing how to think through the components of a decision utilizing decision analysis (i.e., define the problem, elicit objectives, develop alternatives, estimate consequences, and perform trade‐offs). This is best achieved by applying a rapid‐prototyping approach. At each step, decision‐support tools can provide additional insight and clarity, whereas decision‐support frameworks (e.g., priority threat management and systematic conservation planning) can aid navigation of multiple steps of a decision analysis for particular contexts. We summarize key decision‐support frameworks and tools and describe to which step of a decision analysis, and to which contexts, each is most useful to apply. Our introduction to decision science will aid in contextualizing current approaches and new developments, and help decision makers begin to apply decision science to conservation problems.

Software for prioritizing conservation actions based on probabilistic information - Matthew Watts; Carissa J. Klein; Vivitskaia J. D. Tulloch; Silvia B. Carvalho; Hugh P. Possingham (Conservation Biology, 2021)
Marxan is the most common decision‐support tool used to inform the design of protected‐area systems. The original version of Marxan does not consider risk and uncertainty associated with threatening processes affecting protected areas, including uncertainty about the location and condition of species’ populations and habitats now and in the future. We described and examined the functionality of a modified version of Marxan, Marxan with Probability. This software explicitly considers 4 types of uncertainty: probability that a feature exists in a particular place (estimated based on species distribution models or spatially explicit population models); probability that features in a site will be lost in the future due to a threatening process, such as climate change, natural catastrophes, and uncontrolled human interventions; probability that a feature will exist in the future due to natural successional processes, such as a fire or flood; and probability the feature exists but has been degraded by threatening processes, such as overfishing or pollution, and thus cannot contribute to conservation goals. We summarized the results of 5 studies that illustrate how each type of uncertainty can be used to inform protected area design. If there were uncertainty in species or habitat distribution, users could maximize the chance that these features were represented by including uncertainty using Marxan with Probability. Similarly, if threatening processes were considered, users minimized the chance that species or habitats were lost or degraded by using Marxan with Probability. Marxan with Probability opens up substantial new avenues for systematic conservation planning research and application by agencies.

Importance of species translocations under rapid climate change - Nathalie Butt; Alienor L.M. Chauvenet; Vanessa M. Adams; Maria Beger; Rachael V. Gallagher; Danielle F. Shanahan; Michelle Ward; James E.M. Watson; Hugh P. Possingham (Conservation Biology, 2021)
Species that cannot adapt or keep pace with a changing climate are likely to need human intervention to shift to more suitable climates. While hundreds of articles mention using translocation as a climate‐change adaptation tool, in practice, assisted migration as a conservation action remains rare, especially for animals. This is likely due to concern over introducing species to places where they may become invasive. However, there are other barriers to consider, such as time‐frame mismatch, sociopolitical, knowledge and uncertainty barriers to conservationists adopting assisted migration as a go‐to strategy. We recommend the following to advance assisted migration as a conservation tool: attempt assisted migrations at small scales, translocate species with little invasion risk, adopt robust monitoring protocols that trigger an active response, and promote political and public support.

Evaluating surrogates of genetic diversity for conservation planning - Jeffrey O. Hanson; Ana Veríssimo; Guillermo Velo‐Antón; Adam Marques; Miguel Camacho‐Sanchez; Íñigo Martínez‐Solano; Helena Gonçalves; Fernando Sequeira; Hugh P. Possingham; Silvia B. Carvalho (Conservation Biology, 2021)
Protected‐area systems should conserve intraspecific genetic diversity. Because genetic data require resources to obtain, several approaches have been proposed for generating plans for protected‐area systems (prioritizations) when genetic data are not available. Yet such surrogate‐based approaches remain poorly tested. We evaluated the effectiveness of potential surrogate‐based approaches based on microsatellite genetic data collected across the Iberian Peninsula for 7 amphibian and 3 reptilian species. Long‐term environmental suitability did not effectively represent sites containing high genetic diversity (allelic richness). Prioritizations based on long‐term environmental suitability had similar performance to random prioritizations. Geographic distances and resistance distances based on contemporary environmental suitability were not always effective surrogates for identification of combinations of sites that contain individuals with different genetic compositions. Our results demonstrate that population genetic data based on commonly used neutral markers can inform prioritizations, and we could not find an adequate substitute. Conservation planners need to weigh the potential benefits of genetic data against their acquisition costs.

Misinformation, internet honey trading and beekeepers drive a plant invasion - Magdalena Lenda; Piotr Skórka; Karolina Kuszewska; Dawid Moroń; Michał Bełcik; Renata Baczek Kwinta; Franciszek Janowiak; David H. Duncan; Peter A. Vesk; Hugh P. Possingham; Johannes M. H. Knops (Ecology Letters, 2021)
Biological invasions are a major human induced global change that is threatening global biodiversity by homogenizing the world’s fauna and flora. Species spread because humans have moved species across geographical boundaries and have changed ecological factors that structure ecosystems, such as nitrogen deposition, disturbance, etc. Many biological invasions are caused accidentally, as a byproduct of human travel and commerce driven product shipping. However, humans also have spread many species intentionally because of perceived benefits. Of interest is the role of the recent exponential growth in information exchange via internet social media in driving biological invasions. To date, this has not been examined. Here, we show that for one such invasive species, goldenrod, social networks spread misleading and incomplete information that is enhancing the spread of goldenrod invasions into new environments. We show that the notion of goldenrod honey as a “superfood” with unsupported healing properties is driving a demand that leads beekeepers to produce goldenrod honey. Social networks provide a forum for such information exchange and this is leading to further spread of goldenrod in many countries where goldenrod is not native, such as Poland. However, this informal social information exchange ignores laws that focus on preventing the further spread of invasive species and the strong negative effects that goldenrod has on native ecosystems, including floral resources that negatively impact honeybee performance. Thus, scientifically unsupported information on “superfoods” such as goldenrod honey that is disseminated through social internet networks has real world consequences such as increased goldenrod invasions into novel geographical regions which decreases native biodiversity.

Effects of spatial autocorrelation and sampling design on estimates of protected area effectiveness - Pablo Jose Negret; Moreno Di Marco; Laura J. Sonter; Jonathan Rhodes; Hugh P. Possingham; Martine Maron (Conservation Biology, 2020)
Estimating the effectiveness of protected areas (PAs) in reducing deforestation is useful to support decisions on whether to invest in better management of areas already protected or to create new ones. Statistical matching is commonly used to assess this effectiveness, but spatial autocorrelation and regional differences in protection effectiveness are frequently overlooked. Using Colombia as a case study, we employed statistical matching to account for confounding factors in park location and accounted for for spatial autocorrelation to determine statistical significance. We compared the performance of different matching procedures—ways of generating matching pairs at different scales—in estimating PA effectiveness. Differences in matching procedures affected covariate similarity between matched pairs (balance) and estimates of PA effectiveness in reducing deforestation. Independent matching yielded the greatest balance. On average 95% of variables in each region were balanced with independent matching, whereas 33% of variables were balanced when using the method that performed worst. The best estimates suggested that average deforestation inside protected areas in Colombia was 40% lower than in matched sites. Protection significantly reduced deforestation, but PA effectiveness differed among regions. Protected areas in Caribe were the most effective, whereas those in Orinoco and Pacific were least effective. Our results demonstrate that accounting for spatial autocorrelation and using independent matching for each subset of data is needed to infer the effectiveness of protection in reducing deforestation. Not accounting for spatial autocorrelation can distort the assessment of protection effectiveness, increasing type I and II errors and inflating effect size. Our method allowed improved estimates of protection effectiveness across scales and under different conditions and can be applied to other regions to effectively assess PA performance.

Prioritizing debt conversion opportunities for marine conservation - Jennifer McGowan; Rob Weary; Leah Carriere; Edward T. Game; Joanna L. Smith; Melissa Garvey; Hugh P. Possingham (Conservation Biology, 2020)
Incentivized debt conversion is a financing mechanism that can assist countries with a heavy debt burden to bolster their long‐term domestic investment in nature conservation. The Nature Conservancy, an international conservation‐based nongovernmental organization, is adapting debt conversions to support marine conservation efforts by small island developing states and coastal countries. Prioritizing debt conversion opportunities according to their potential return on investment can increase the impact and effectiveness of this finance mechanism. We developed guidance on how to do so with a decision‐support approach that relies on a novel threat‐based adaptation of cost‐effectiveness analysis. We constructed scenarios by varying parameters of the approach, including enabling conditions, expected benefits, and threat classifications. Incorporating both abatable and unabatable threats affected priorities across planning scenarios. Similarly, differences in scenario construction resulted in unique solution sets for top priorities. We show how environmental organizations, private entities, and investment banks can adopt structured prioritization frameworks for making decisions about conservation finance investments, such as debt conversions. Our guidance can accommodate a suite of social, ecological, and economic considerations, making the approach broadly applicable to other conservation finance mechanisms or investment strategies that seek to establish a transparent process for return‐on‐investment decision‐making.

Effects of amusing memes on concern for unappealing species - Magdalena Lenda; Pjoter Skórka; Błażej Mazur; William Sutherland; Piotr Tryjanowski; Dawid Moroń; Erik Meijaard; Hugh P. Possingham; Kerrie A. Wilson (Conservation Biology, 2020)
There is limited knowledge of the mechanisms that can inspire people's concern and engagement in the protection of unpopular and unappealing species. We analyzed Polish people's interest in themed internet memes featuring the proboscis monkey ( Nasalis larvatus ) and the consequences of this interest for conservation marketing. We examined Google Trends data, used Google Search, and searched popular media materials to estimate interest in the proboscis monkey in Poland. Photos of the proboscis monkey when presented with humor in internet memes attracted as much interest as usually more popular species (e.g., koala, panda, and orangutan) used in marketing by nongovernmental organizations. Amusing internet memes spread by social media positively correlated with increasing interest in the unappealing species, such as proboscis monkey. Interest in amusing internet memes positively correlated with individuals’ decisions to donate to 6 crowdfunding actions. Thus, conservation marketing that includes amusing memes and social media may provide a worthwhile complement to traditional campaigns and are likely to influence individuals who are unaffected by the usual means.

Use of surrogate species to cost‐effectively prioritize conservation actions - Michelle Ward; Jonathan R. Rhodes; James E.M. Watson; James Lefevre; Scott Atkinson; Hugh P. Possingham (Conservation Biology, 2020)
Conservation efforts often focus on umbrella species whose distributions overlap with many other flora and fauna. However, because biodiversity is affected by different threats that are spatially variable, focusing only on the geographic range overlap of species may not be sufficient in allocating the necessary actions needed to efficiently abate threats. We developed a problem‐based method for prioritizing conservation actions for umbrella species that maximizes the total number of flora and fauna benefiting from management while considering threats, actions, and costs. We tested our new method by assessing the performance of the Australian federal government's umbrella prioritization list, which identifies 73 umbrella species as priorities for conservation attention. Our results show that the federal government priority list benefits only 6% of all Australia's threatened terrestrial species. This could be increased to benefit nearly half (or 46%) of all threatened terrestrial species for the same budget of AU$550 million/year if more suitable umbrella species were chosen. This results in a 7‐fold increase in management efficiency. We believe nations around the world can markedly improve the selection of prioritized umbrella species for conservation action with this transparent, quantitative, and objective prioritization approach.

Support for the habitat amount hypothesis from a global synthesis of species density studies - James I. Watling; Victor Arroyo‐Rodríguez; Marion Pfeifer; Lander Baeten; Cristina Banks‐Leite; Laura M. Cisneros; Rebecca Fang; A. Caroli Hamel‐Leigue; Thibault Lachat; Inara R. Leal; Luc Lens; Hugh P. Possingham; et al. (Ecology Letters, 2020)
Decades of research suggest that species richness depends on spatial characteristics of habitat patches, especially their size and isolation. In contrast, the habitat amount hypothesis predicts that (1) species richness in plots of fixed size (species density) is more strongly and positively related to the amount of habitat around the plot than to patch size or isolation; (2) habitat amount better predicts species density than patch size and isolation combined, (3) there is no effect of habitat fragmentation per se on species density and (4) patch size and isolation effects do not become stronger with declining habitat amount. Data on eight taxonomic groups from 35 studies around the world support these predictions. Conserving species density requires minimising habitat loss, irrespective of the configuration of the patches in which that habitat is contained.

UN Decade on Ecosystem Restoration 2021–2030—What Chance for Success in Restoring Coastal Ecosystems? - Nathan J. Waltham; Michael Elliott; Shing Yip Lee; Catherine Lovelock; Carlos M. Duarte; Christina Buelow; Charles Simenstad; Ivan Nagelkerken; Louw Claassens; Colin K-C Wen; Mario Barletta; Rod M. Connolly; et al. (Frontiers in Marine Science, 2020)

The human footprint represents observable human pressures: Reply to Kennedy et al. - Oscar Venter; Hugh P. Possingham; James E. M. Watson (Global Change Biology, 2020)

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

Using individual‐based movement information to identify spatial conservation priorities for mobile species - Ross G. Dwyer; Hamish A. Campbell; Richard D. Pillans; Matthew E. Watts; Barry J. Lyon; Siddeswara M. Guru; Minh N. Dinh; Hugh P. Possingham; Craig E. Franklin (Conservation Biology, 2019)
The optimal design of reserve networks and fisheries closures depends on species occurrence information and knowledge of how anthropogenic impacts interact with the species concerned. However, challenges in surveying mobile and cryptic species over adequate spatial and temporal scales can mask the importance of particular habitats, leading to uncertainty about which areas to protect to optimize conservation efforts. We investigated how telemetry‐derived locations can help guide the scale and timing of fisheries closures with the aim of reducing threatened species bycatch. Forty juvenile speartooth sharks ( Glyphis glyphis ) were monitored over 22 months with implanted acoustic transmitters and an array of hydrophone receivers. Using the decision‐support tool Marxan, we formulated a permanent fisheries closure that prioritized areas used more frequently by tagged sharks and considered areas perceived as having high value to fisheries. To explore how the size of the permanent closure compared with an alternative set of time‐area closures (i.e., where different areas were closed to fishing at different times of year), we used a cluster analysis to group months that had similar arrangements of selected planning units (informed by shark movements during that month) into 2 time‐area closures. Sharks were consistent in their timing and direction of migratory movements, but the number of tagged sharks made a big difference in the placement of the permanent closure; 30 individuals were needed to capture behavioral heterogeneity. The dry‐season (May–January) and wet‐season (February–April) time‐area closures opened 20% and 25% more planning units to fishing, respectively, compared with the permanent closure with boundaries fixed in space and time. Our results show that telemetry has the potential to inform and improve spatial management of mobile species and that the temporal component of tracking data can be incorporated into prioritizations to reduce possible impacts of spatial closures on established fisheries.

Quantifying biases in marine‐protected‐area placement relative to abatable threats - Caitlin D. Kuempel; Kendall R. Jones; James E.M. Watson; Hugh P. Possingham (Conservation Biology, 2019)
Marine protected areas (MPAs) are a critical defense against biodiversity loss in the world's oceans, but to realize near‐term conservation benefits, they must be established where major threats to biodiversity occur and can be mitigated. We quantified the degree to which MPA establishment has targeted stoppable threats (i.e., threats that can be abated through effectively managed MPAs alone) by combining spatially explicit marine biodiversity threat data in 2008 and 2013 and information on the location and potential of MPAs to halt threats. We calculated an impact metric to determine whether countries are protecting proportionally more high‐ or low‐threat ecoregions and compared observed values with random protected‐area allocation. We found that protection covered

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

A habitat‐based approach to predict impacts of marine protected areas on fishers - João B. Teixeira; Rodrigo L. Moura; Morena Mills; Carissa Klein; Christopher J. Brown; Vanessa M. Adams; Hedley Grantham; Matthew Watts; Deborah Faria; Gilberto M. Amado‐Filho; Alex C. Bastos; Reinaldo Lourival; et al. (Conservation Biology, 2018)
Although marine protected areas can simultaneously contribute to biodiversity conservation and fisheries management, the global network is biased toward particular ecosystem types because they have been established primarily in an ad hoc fashion. The optimization of trade‐offs between biodiversity benefits and socioeconomic values increases success of protected areas and minimizes enforcement costs in the long run, but it is often neglected in marine spatial planning (MSP). Although the acquisition of spatially explicit socioeconomic data is perceived as a costly or secondary step in MSP, it is critical to account for lost opportunities by people whose activities will be restricted, especially fishers. We developed an easily reproduced habitat‐based approach to estimate the spatial distribution of opportunity cost to fishers in data‐poor regions. We assumed the most accessible areas have higher economic and conservation values than less accessible areas and their designation as no‐take zones represents a loss of fishing opportunities. We estimated potential distribution of fishing resources from bathymetric ranges and benthic habitat distribution and the relative importance of the different resources for each port of total catches, revenues, and stakeholder perception. In our model, we combined different cost layers to produce a comprehensive cost layer so that we could evaluate of trade‐offs. Our approach directly supports conservation planning, can be applied generally, and is expected to facilitate stakeholder input and community acceptance of conservation.

Addressing transboundary conservation challenges through marine spatial prioritization - Elena Gissi; Jennifer McGowan; Chiara Venier; Davide Di Carlo; Francesco Musco; Stefano Menegon; Peter Mackelworth; Tundi Agardy; Hugh Possingham (Conservation Biology, 2018)
The Adriatic and Ionian Region is an important area for both strategic maritime development and biodiversity conservation in the European Union (EU). However, given that both EU and non‐EU countries border the sea, multiple legal and regulatory frameworks operate at different scales, which can hinder the coordinated long‐term sustainable development of the region. Transboundary marine spatial planning can help overcome these challenges by building consensus on planning objectives and making the trade‐offs between biodiversity conservation and its influence on economically important sectors more explicit. We address this challenge by developing and testing 4 spatial prioritization strategies with the decision‐support tool Marxan, which meets targets for biodiversity conservation while minimizing impacts to users. We evaluated these strategies in terms of how priority areas shift under different scales of target setting (e.g., regional vs. country level). We also examined the trade‐off between cost‐efficiency and how equally solutions represent countries and maritime industries ( n = 14) operating in the region with the protection‐equality metric. We found negligible differences in where priority conservation areas were located when we set targets for biodiversity at the regional versus country scale. Conversely, the prospective impacts on industries, when considered as costs to be minimized, were highly divergent across scenarios and biased the placement of protection toward industries located in isolation or where there were few other industries. We recommend underpinning future marine spatial planning efforts in the region through identification of areas of national significance, transboundary areas requiring cooperation between countries, and areas where impacts on maritime industries require careful consideration of the trade‐off between biodiversity conservation and socioeconomic objectives.

Correction to: A theory for ecological survey methods to map individual distributions - Nao Takashina; Maria Beger; Buntarou Kusumoto; Suren Rathnayake; Hugh P. Possingham (Theoretical Ecology, 2018)

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

Correction to: Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

A theory for ecological survey methods to map individual distributions - Nao Takashina; Maria Beger; Buntarou Kusumoto; Suren Rathnayake; Hugh P. Possingham (Theoretical Ecology, 2018)

The extent and predictability of the biodiversity–carbon correlation - Moreno Di Marco; James E. M. Watson; David J. Currie; Hugh P. Possingham; Oscar Venter (Ecology Letters, 2018)
Protecting biomass carbon stocks to mitigate climate change has direct implications for biodiversity conservation. Yet, evidence that a positive association exists between carbon density and species richness is contrasting. Here, we test how this association varies (1) across spatial extents and (2) as a function of how strongly carbon and species richness depend on environmental variables. We found the correlation weakens when moving from larger extents, e.g. realms, to narrower extents, e.g. ecoregions. For ecoregions, a positive correlation emerges when both species richness and carbon density vary as functions of the same environmental variables (climate, soil, elevation). In 20% of tropical ecoregions, there are opportunities to pursue carbon conservation with direct biodiversity co‐benefits, while other ecoregions require careful planning for both species and carbon to avoid potentially perverse outcomes. The broad assumption of a linear relationship between carbon and biodiversity can lead to undesired outcomes.

Bias in protected‐area location and its effects on long‐term aspirations of biodiversity conventions - Oscar Venter; Ainhoa Magrach; Nick Outram; Carissa Joy Klein; Hugh P. Possingham; Moreno Di Marco; James E.M. Watson (Conservation Biology, 2018)
To contribute to the aspirations of recent international biodiversity conventions, protected areas (PAs) must be strategically located and not simply established on economically marginal lands as they have in the past. With refined international commitments under the Convention on Biological Diversity to target protected areas in places of “importance to biodiversity,” perhaps they may now be. We analyzed location biases in PAs globally over historic (pre‐2004) and recent periods. Specifically, we examined whether the location of protected areas are more closely associated with high concentrations of threatened vertebrate species or with areas of low agricultural opportunity costs. We found that both old and new protected areas did not target places with high concentrations of threatened vertebrate species. Instead, they appeared to be established in locations that minimize conflict with agriculturally suitable lands. This entrenchment of past trends has substantial implications for the contributions these protected areas are making to international commitments to conserve biodiversity. If protected‐area growth from 2004 to 2014 had strategically targeted unrepresented threatened vertebrates, >30 times more species (3086 or 2553 potential vs. 85 actual new species represented) would have been protected for the same area or the same cost as the actual expansion. With the land available for conservation declining, nations must urgently focus new protection on places that provide for the conservation outcomes outlined in international treaties.

Trade‐offs in triple‐bottom‐line outcomes when recovering fisheries - Christopher J Brown; Glenn Althor; Benjamin S Halpern; Md Sayed Iftekhar; Carissa J Klein; Simon Linke; Elizabeth C Pryde; Steven Schilizzi; James E M Watson; Becky Twohey; Hugh P Possingham (Fish and Fisheries, 2018)
Almost all environmental management comes at an economic cost that may not be borne equitably by all stakeholders. Here, we investigate how heterogeneity in catch and profits among fishers influences the trade‐off among the triple‐bottom‐line objectives of recovering a fish population, maximizing its economic value and distributing restrictions equitably across fishers. As a case‐study, we examine management reform of an ecologically and economically important coral reef fishery operating within the Great Barrier Reef Marine Park. Using a simulation model, we find that total profitability of the fishing industry is 40% lower if recovery plans are equitable when compared to the most economically efficient plan. However, efficient recovery plans were typically highly inequitable because they required some fishers to cease fishing. Equity was defined according to different norms, and the efficiency loss was greatest when catch losses were shared equally across fishers rather than in proportion to their historical catch. We then varied key social, economic and biological parameters to identify cases when equity and efficient recovery would trade‐off most strongly. Recovery plans could be both efficient and equitable when heterogeneity in fisher's catches and individual catch efficiencies was lower. If fishers were homogenous then equitable plans could have maximal economic efficiency. These results emphasize the importance of considering heterogeneity in individual fishers when designing recovery plans. Recovery plans that are inequitable may often fail to gain stakeholder support, so in fisheries with high heterogeneity we should temper our expectations for marked increases in profits.

Setting conservation priorities for migratory networks under uncertainty - Kiran L. Dhanjal‐Adams; Marcel Klaassen; Sam Nicol; Hugh P. Possingham; Iadine Chadès; Richard A. Fuller (Conservation Biology, 2017)
Conserving migratory species requires protecting connected habitat along the pathways they travel. Despite recent improvements in tracking animal movements, migratory connectivity remains poorly resolved at a population level for the vast majority of species, thus conservation prioritization is hampered. To address this data limitation, we developed a novel approach to spatial prioritization based on a model of potential connectivity derived from empirical data on species abundance and distance traveled between sites during migration. We applied the approach to migratory shorebirds of the East Asian‐Australasian Flyway. Conservation strategies that prioritized sites based on connectivity and abundance metrics together maintained larger populations of birds than strategies that prioritized sites based only on abundance metrics. The conservation value of a site therefore depended on both its capacity to support migratory animals and its position within the migratory pathway; the loss of crucial sites led to partial or total population collapse. We suggest that conservation approaches that prioritize sites supporting large populations of migrants should, where possible, also include data on the spatial arrangement of sites.

Incorporating climate change into ecosystem service assessments and decisions: a review - Rebecca K. Runting; Brett A. Bryan; Laura E. Dee; Fleur J. F. Maseyk; Lisa Mandle; Perrine Hamel; Kerrie A. Wilson; Kathleen Yetka; Hugh P. Possingham; Jonathan R. Rhodes (Global Change Biology, 2017)
Climate change is having a significant impact on ecosystem services and is likely to become increasingly important as this phenomenon intensifies. Future impacts can be difficult to assess as they often involve long timescales, dynamic systems with high uncertainties, and are typically confounded by other drivers of change. Despite a growing literature on climate change impacts on ecosystem services, no quantitative syntheses exist. Hence, we lack an overarching understanding of the impacts of climate change, how they are being assessed, and the extent to which other drivers, uncertainties, and decision making are incorporated. To address this, we systematically reviewed the peer‐reviewed literature that assesses climate change impacts on ecosystem services at subglobal scales. We found that the impact of climate change on most types of services was predominantly negative (59% negative, 24% mixed, 4% neutral, 13% positive), but varied across services, drivers, and assessment methods. Although uncertainty was usually incorporated, there were substantial gaps in the sources of uncertainty included, along with the methods used to incorporate them. We found that relatively few studies integrated decision making, and even fewer studies aimed to identify solutions that were robust to uncertainty. For management or policy to ensure the delivery of ecosystem services, integrated approaches that incorporate multiple drivers of change and account for multiple sources of uncertainty are needed. This is undoubtedly a challenging task, but ignoring these complexities can result in misleading assessments of the impacts of climate change, suboptimal management outcomes, and the inefficient allocation of resources for climate adaptation.

Controlling range expansion in habitat networks by adaptively targeting source populations - Karlo Hock; Nicholas H. Wolff; Roger Beeden; Jessica Hoey; Scott A. Condie; Kenneth R. N. Anthony; Hugh P. Possingham; Peter J. Mumby (Conservation Biology, 2016)
Controlling the spread of invasive species, pests, and pathogens is often logistically limited to interventions that target specific locations at specific periods. However, in complex, highly connected systems, such as marine environments connected by ocean currents, populations spread dynamically in both space and time via transient connectivity links. This results in nondeterministic future distributions of species in which local populations emerge dynamically and concurrently over a large area. The challenge, therefore, is to choose intervention locations that will maximize the effectiveness of the control efforts. We propose a novel method to manage dynamic species invasions and outbreaks that identifies the intervention locations most likely to curtail population expansion by selectively targeting local populations most likely to expand their future range. Critically, at any point during the development of the invasion or outbreak, the method identifies the local intervention that maximizes the long‐term benefit across the ecosystem by restricting species’ potential to spread. In so doing, the method adaptively selects the intervention targets under dynamically changing circumstances. To illustrate the effectiveness of the method we applied it to controlling the spread of crown‐of‐thorns starfish ( Acanthaster sp.) outbreaks across Australia's Great Barrier Reef. Application of our method resulted in an 18‐fold relative improvement in management outcomes compared with a random targeting of reefs in putative starfish control scenarios. Although we focused on applying the method to reducing the spread of an unwanted species, it can also be used to facilitate the spread of desirable species through connectivity networks. For example, the method could be used to select those fragments of habitat most likely to rebuild a population if they were sufficiently well protected.

The value of migration information for conservation prioritization of sea turtles in the Mediterranean - Tessa Mazor; Maria Beger; Jennifer McGowan; Hugh P. Possingham; Salit Kark (Global Ecology and Biogeography, 2016)
Aim Conservation plans often struggle to account for connectivity in spatial prioritization approaches for the protection of migratory species. Protection of such species is challenging because their movements may be uncertain and variable, span vast distances, cross international borders and traverse land and sea habitats. Often we are faced with small samples of information from various sources and the collection of additional data can be costly and time‐consuming. Therefore it is important to evaluate what degree of spatial information provides sufficient results for directing management actions. Here we develop and evaluate an approach that incorporates habitat and movement information to advance the conservation of migratory species. We test our approach using information on threatened loggerhead sea turtles ( C aretta caretta ) in the M editerranean. Location The M editerranean S ea. Methods We use Marxan, a spatially explicit decision support tool, to select priority conservation areas. Four approaches with increasing amounts of information about the loggerhead sea turtle are compared, ranging from (1) the broad distribution, (2) multiple habitat types that represent foraging, nesting and inter‐nesting habitats, (3) mark–recapture movement information to (4) telemetry‐derived migration tracks. Results We find that spatial priorities for sea turtle conservation are sensitive to the information used in the prioritization process. Setting conservation targets for migration tracks altered the location of conservation priorities, indicating that conservation plans designed without such data would miss important sea turtle habitat. We discover that even a small number of tracks make a significant contribution to a spatial conservation plan if those tracks are substantially different. Main conclusions This study presents a novel approach to improving spatial prioritization for conserving migratory species. We propose that future telemetry studies tailor their efforts towards conservation prioritization needs, meaning that spatially dispersed samples rather than just large numbers should be obtained. This work highlights the valuable information that telemetry research contributes to the conservation of migratory species.

Bolder science needed now for protected areas - James E. M. Watson; Emily S. Darling; Oscar Venter; Martine Maron; Joe Walston; Hugh P. Possingham; Nigel Dudley; Marc Hockings; Megan Barnes; Thomas M. Brooks (Conservation Biology, 2016)
Recognizing that protected areas (PAs) are essential for effective biodiversity conservation action, the Convention on Biological Diversity established ambitious PA targets as part of the 2020 Strategic Plan for Biodiversity. Under the strategic goal to “improve the status of biodiversity by safeguarding ecosystems, species, and genetic diversity,” Target 11 aims to put 17% of terrestrial and 10% of marine regions under PA status by 2020. Additionally and crucially, these areas are required to be of particular importance for biodiversity and ecosystem services, effectively and equitably managed, ecologically representative, and well‐connected and to include “other effective area‐based conservation measures” (OECMs). Whereas the area‐based targets are explicit and measurable, the lack of guidance for what constitutes important and representative ; effective ; and OECMs is affecting how nations are implementing the target. There is a real risk that Target 11 may be achieved in terms of area while failing the overall strategic goal for which it is established because the areas are poorly located, inadequately managed, or based on unjustifiable inclusion of OECMs. We argue that the conservation science community can help establish ecologically sensible PA targets to help prioritize important biodiversity areas and achieve ecological representation; identify clear, comparable performance metrics of ecological effectiveness so progress toward these targets can be assessed; and identify metrics and report on the contribution OECMs make toward the target. By providing ecologically sensible targets and new performance metrics for measuring the effectiveness of both PAs and OECMs, the science community can actively ensure that the achievement of the required area in Target 11 is not simply an end in itself but generates genuine benefits for biodiversity.

Quantifying the relative irreplaceability of important bird and biodiversity areas - Moreno Di Marco; Thomas Brooks; Annabelle Cuttelod; Lincoln D.C. Fishpool; Carlo Rondinini; Robert J. Smith; Leon Bennun; Stuart H.M. Butchart; Simon Ferrier; Ruud P.B. Foppen; Lucas Joppa; Diego Juffe‐Bignoli; et al. (Conservation Biology, 2016)
World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.

Seascape features, rather than dispersal traits, predict spatial genetic patterns in co‐distributed reef fishes - Libby Liggins; Eric A. Treml; Hugh P. Possingham; Cynthia Riginos (Journal of Biogeography, 2016)
Aim To determine which seascape features have shaped the spatial genetic patterns of coral reef fishes, and to identify common patterns among species related to dispersal traits [egg type and pelagic larval duration ( PLD )]. Location Indian and Pacific Oceans, including the Indo‐Australian Archipelago. Methods We sampled coral reef fishes with differing dispersal traits ( Pomacentrus coelestis , Dascyllus trimaculatus , Hailchoeres hortulanus and Acanthurus triostegus ) and characterized spatial (mt DNA ) genetic patterns using AMOVA ‐clustering and measures of genetic differentiation. Similarity in the spatial genetic patterns among species was assessed using the congruence among distance matrices method and the seascape features associated with the genetic differentiation of each species were identified using multiple regression of distance matrices ( MRDM ) and stepwise model selection. Results Similar spatial genetic patterns were found for P. coelestis and H. hortulanus, despite their differing egg type (benthic versus pelagic). MRDM indicated that geographical distance was underlying their correlated genetic patterns. Species with pelagic eggs ( A. triostegus and H. hortulanus ) also had correlated patterns of genetic differentiation ( D est ); however, a common underlying seascape feature could not be inferred. Additionally, the common influence of the Torres Strait and the Lydekker/Weber's line was identified for the genetic patterns of differentiation for P. coelestis and A. triostegus , despite their differing dispersal traits, and the uncorrelated spatial genetic patterns of these species. Main conclusions Our study demonstrates the value of a quantitative, hypothesis‐testing framework in comparative phylogeography. We found that dispersal traits (egg type and PLD ) did not predict which species had similar spatial genetic patterns or which seascape features were associated with these patterns. Furthermore, even in the absence of visually similar, or correlated spatial genetic patterns, our approach enabled us to identify seascape features that had a common influence on the spatial genetic patterns of co‐distributed species.

Effects of threat management interactions on conservation priorities - Nancy A. Auerbach; Kerrie A. Wilson; Ayesha I.T. Tulloch; Jonathan R. Rhodes; Jeffrey O. Hanson; Hugh P. Possingham (Conservation Biology, 2015)
Decisions need to be made about which biodiversity management actions are undertaken to mitigate threats and about where these actions are implemented. However, management actions can interact; that is, the cost, benefit, and feasibility of one action can change when another action is undertaken. There is little guidance on how to explicitly and efficiently prioritize management for multiple threats, including deciding where to act. Integrated management could focus on one management action to abate a dominant threat or on a strategy comprising multiple actions to abate multiple threats. Furthermore management could be undertaken at sites that are in close proximity to reduce costs. We used cost‐effectiveness analysis to prioritize investments in fire management, controlling invasive predators, and reducing grazing pressure in a bio‐diverse region of southeastern Queensland, Australia. We compared outcomes of 5 management approaches based on different assumptions about interactions and quantified how investment needed, benefits expected, and the locations prioritized for implementation differed when interactions were taken into account. Managing for interactions altered decisions about where to invest and in which actions to invest and had the potential to deliver increased investment efficiency. Differences in high priority locations and actions were greatest between the approaches when we made different assumptions about how management actions deliver benefits through threat abatement: either all threats must be managed to conserve species or only one management action may be required. Threatened species management that does not consider interactions between actions may result in misplaced investments or misguided expectations of the effort required to mitigate threats to species .

Priority threat management of invasive animals to protect biodiversity under climate change - Jennifer Firn; Ramona Maggini; Iadine Chadès; Sam Nicol; Belinda Walters; Andy Reeson; Tara G. Martin; Hugh P. Possingham; Jean‐Baptiste Pichancourt; Rocio Ponce‐Reyes; Josie Carwardine (Global Change Biology, 2015)
Climate change is a major threat to global biodiversity, and its impacts can act synergistically to heighten the severity of other threats. Most research on projecting species range shifts under climate change has not been translated to informing priority management strategies on the ground. We develop a prioritization framework to assess strategies for managing threats to biodiversity under climate change and apply it to the management of invasive animal species across one‐sixth of the Australian continent, the Lake Eyre Basin. We collected information from key stakeholders and experts on the impacts of invasive animals on 148 of the region's most threatened species and 11 potential strategies. Assisted by models of current distributions of threatened species and their projected distributions, experts estimated the cost, feasibility, and potential benefits of each strategy for improving the persistence of threatened species with and without climate change. We discover that the relative cost‐effectiveness of invasive animal control strategies is robust to climate change, with the management of feral pigs being the highest priority for conserving threatened species overall. Complementary sets of strategies to protect as many threatened species as possible under limited budgets change when climate change is considered, with additional strategies required to avoid impending extinctions from the region. Overall, we find that the ranking of strategies by cost‐effectiveness was relatively unaffected by including climate change into decision‐making, even though the benefits of the strategies were lower. Future climate conditions and impacts on range shifts become most important to consider when designing comprehensive management plans for the control of invasive animals under limited budgets to maximize the number of threatened species that can be protected.

Two additional principles for determining which species to monitor - Howard B. Wilson; Jonathan R. Rhodes; Hugh P. Possingham (Ecology, 2015)
Monitoring to detect population declines is widespread, but also costly. There is, consequently, a need to optimize monitoring to maximize cost‐effectiveness. Here we develop a quantitative decision analysis framework for how to optimally allocate resources for monitoring among species. By keeping the framework simple, we analytically establish two new principles about which species are optimal to monitor for detecting declines: (1) those that lie on the boundary between species being allocated resources for conservation action and species that are not and (2) those with the greatest uncertainty in whether they are declining. These two principles are in addition to other factors that are also important in monitoring decisions, such as complementarity. We demonstrate the efficacy of these principles when other factors are not present, and show how the two principles can be combined. This analysis demonstrates that the most cost‐effective species to monitor are ones where the information gained from monitoring is most likely to change the allocation of funds for action, not necessarily the most vulnerable or endangered. We suggest these results are general and apply to all ecological monitoring, not just of biological species: monitoring and information are only valuable when they are likely to change how people act.

Towards a framework for assessment and management of cumulative human impacts on marine food webs - Sylvaine Giakoumi; Benjamin S. Halpern; Loïc N. Michel; Sylvie Gobert; Maria Sini; Charles‐François Boudouresque; Maria‐Cristina Gambi; Stelios Katsanevakis; Pierre Lejeune; Monica Montefalcone; Gerard Pergent; Christine Pergent‐Martini; et al. (Conservation Biology, 2015)
Effective ecosystem‐based management requires understanding ecosystem responses to multiple human threats, rather than focusing on single threats. To understand ecosystem responses to anthropogenic threats holistically, it is necessary to know how threats affect different components within ecosystems and ultimately alter ecosystem functioning. We used a case study of a Mediterranean seagrass (Posidonia oceanica) food web and expert knowledge elicitation in an application of the initial steps of a framework for assessment of cumulative human impacts on food webs. We produced a conceptual seagrass food web model, determined the main trophic relationships, identified the main threats to the food web components, and assessed the components’ vulnerability to those threats. Some threats had high (e.g., coastal infrastructure) or low impacts (e.g., agricultural runoff) on all food web components, whereas others (e.g., introduced carnivores) had very different impacts on each component. Partitioning the ecosystem into its components enabled us to identify threats previously overlooked and to reevaluate the importance of threats commonly perceived as major. By incorporating this understanding of system vulnerability with data on changes in the state of each threat (e.g., decreasing domestic pollution and increasing fishing) into a food web model, managers may be better able to estimate and predict cumulative human impacts on ecosystems and to prioritize conservation actions.

Current practices in the identification of critical habitat for threatened species - Abbey E. Camaclang; Martine Maron; Tara G. Martin; Hugh P. Possingham (Conservation Biology, 2015)
The term critical habitat is used to describe the subset of habitat that is essential to the survival and recovery of species. Some countries legally require that critical habitat of listed threatened and endangered species be identified and protected. However, there is little evidence to suggest that the identification of critical habitat has had much impact on species recovery. We hypothesized that this may be due at least partly to a mismatch between the intent of critical habitat identification, which is to protect sufficient habitat for species persistence and recovery, and its practice. We used content analysis to systematically review critical habitat documents from the United States, Canada, and Australia. In particular, we identified the major trends in type of information used to identify critical habitat and in occupancy of habitat identified as critical. Information about population viability was used to identify critical habitat for only 1% of the species reviewed, and for most species, designated critical habitat did not include unoccupied habitat. Without reference to population viability, it is difficult to determine how much of a species’ occupied and unoccupied habitat will be required for persistence. We therefore conclude that the identification of critical habitat remains inconsistent with the goal of protecting sufficient habitat to support persistence and recovery of the species. Ensuring that critical habitat identification aligns more closely with its intent will improve the accuracy of the designations and may therefore help improve the benefits to species recovery when combined with adequate implementation and enforcement of legal protections .

Effect of risk aversion on prioritizing conservation projects - Ayesha I.T. Tulloch; Richard F. Maloney; Liana N. Joseph; Joseph R. Bennett; Martina M.I. Di Fonzo; William J.M. Probert; Shaun M. O'Connor; Jodie P. Densem; Hugh P. Possingham (Conservation Biology, 2015)
Conservation outcomes are uncertain. Agencies making decisions about what threat mitigation actions to take to save which species frequently face the dilemma of whether to invest in actions with high probability of success and guaranteed benefits or to choose projects with a greater risk of failure that might provide higher benefits if they succeed. The answer to this dilemma lies in the decision maker's aversion to risk—their unwillingness to accept uncertain outcomes. Little guidance exists on how risk preferences affect conservation investment priorities. Using a prioritization approach based on cost effectiveness, we compared 2 approaches: a conservative probability threshold approach that excludes investment in projects with a risk of management failure greater than a fixed level, and a variance‐discounting heuristic used in economics that explicitly accounts for risk tolerance and the probabilities of management success and failure. We applied both approaches to prioritizing projects for 700 of New Zealand's threatened species across 8303 management actions. Both decision makers’ risk tolerance and our choice of approach to dealing with risk preferences drove the prioritization solution (i.e., the species selected for management). Use of a probability threshold minimized uncertainty, but more expensive projects were selected than with variance discounting, which maximized expected benefits by selecting the management of species with higher extinction risk and higher conservation value. Explicitly incorporating risk preferences within the decision making process reduced the number of species expected to be safe from extinction because lower risk tolerance resulted in more species being excluded from management, but the approach allowed decision makers to choose a level of acceptable risk that fit with their ability to accommodate failure. We argue for transparency in risk tolerance and recommend that decision makers accept risk in an adaptive management framework to maximize benefits and avoid potential extinctions due to inefficient allocation of limited resources. El Efecto de la Aversión de Riesgo sobre la Priorización de Proyectos de Conservación

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Water Planning and Hydro-Climatic Change in the Murray-Darling Basin, Australia - R. Quentin Grafton; Jamie Pittock; John Williams; Qiang Jiang; Hugh Possingham; John Quiggin (Ambio, 2014)

Determining When to Change Course in Management Actions - CHOOI FEI NG; MICHAEL A. MCCARTHY; TARA G. MARTIN; HUGH P. POSSINGHAM (Conservation Biology, 2014)
Time is of the essence in conservation biology. To secure the persistence of a species, we need to understand how to balance time spent among different management actions. A new and simple method to test the efficacy of a range of conservation actions is required. Thus, we devised a general theoretical framework to help determine whether to test a new action and when to cease a trial and revert to an existing action if the new action did not perform well. The framework involves constructing a general population model under the different management actions and specifying a management objective. By maximizing the management objective, we could generate an analytical solution that identifies the optimal timing of when to change management action. We applied the analytical solution to the case of the Christmas Island pipistrelle bat (Pipistrelle murrayi) , a species for which captive breeding might have prevented its extinction. For this case, we used our model to determine whether to start a captive breeding program and when to stop a captive breeding program and revert to managing the species in the wild, given that the management goal is to maximize the chance of reaching a target wild population size. For the pipistrelle bat, captive breeding was to start immediately and it was desirable to place the species in captivity for the entire management period. The optimal time to revert to managing the species in the wild was driven by several key parameters, including the management goal, management time frame, and the growth rates of the population under different management actions. Knowing when to change management actions can help conservation managers’ act in a timely fashion to avoid species extinction. Determinar Cuándo Cambiar el Rumbo en las Acciones de Manejo

Optimal Management of a Multispecies Shorebird Flyway under Sea‐Level Rise - TAKUYA IWAMURA; RICHARD A. FULLER; HUGH P. POSSINGHAM (Conservation Biology, 2014)
Every year, millions of migratory shorebirds fly through the East Asian–Australasian Flyway between their arctic breeding grounds and Australasia. This flyway includes numerous coastal wetlands in Asia and the Pacific that are used as stopover sites where birds rest and feed. Loss of a few important stopover sites through sea‐level rise (SLR) could cause sudden population declines. We formulated and solved mathematically the problem of how to identify the most important stopover sites to minimize losses of bird populations across flyways by conserving land that facilitates upshore shifts of tidal flats in response to SLR. To guide conservation investment that minimizes losses of migratory bird populations during migration, we developed a spatially explicit flyway model coupled with a maximum flow algorithm. Migratory routes of 10 shorebird taxa were modeled in a graph theoretic framework by representing clusters of important wetlands as nodes and the number of birds flying between 2 nodes as edges. We also evaluated several resource allocation algorithms that required only partial information on flyway connectivity (node strategy, based on the impacts of SLR at nodes; habitat strategy, based on habitat change at sites; population strategy, based on population change at sites; and random investment). The resource allocation algorithms based on flyway information performed on average 15% better than simpler allocations based on patterns of habitat loss or local bird counts. The Yellow Sea region stood out as the most important priority for effective conservation of migratory shorebirds, but investment in this area alone will not ensure the persistence of species across the flyway. The spatial distribution of conservation investments differed enormously according to the severity of SLR and whether information about flyway connectivity was used to guide the prioritizations. With the rapid ongoing loss of coastal wetlands globally, our method provides insight into efficient conservation planning for migratory species. Gestión Óptima de una Ruta Migratoria de Múltiples Especies de Aves Costeras Sometida a Incremento del Nivel del Mar

The control of rank-abundance distributions by a competitive despotic species - Ralph Mac Nally; Clive A. McAlpine; Hugh P. Possingham; Martine Maron (Oecologia, 2014)

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate - MORENA MILLS; SAM NICOL; JESSIE A. WELLS; JOSÉ J. LAHOZ‐MONFORT; BRENDAN WINTLE; MICHAEL BODE; MARTIN WARDROP; TERRY WALSHE; WILLIAM J. M. PROBERT; MICHAEL C. RUNGE; HUGH P. POSSINGHAM; EVE MCDONALD MADDEN (Conservation Biology, 2014)
Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate‐change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that integrates these costs and benefits with probabilistic forecasts for the extent of sea‐level rise to find a balance between coastal ecosystem protection and moderate coastal development. Here, we suggest that instead of keeping their options open managers should incorporate uncertain sea‐level rise predictions into a decision‐making framework that evaluates the benefits and costs of conservation and development. In our example, based on plausible scenarios for sea‐level rise and assuming a risk‐neutral decision maker, we found that substantial development could be accommodated with negligible loss of environmental assets. Characterization of the Pareto efficiency of conservation and development outcomes provides valuable insight into the intensity of trade‐offs between development and conservation. However, additional work is required to improve understanding of the consequences of alternative spatial plans and the value judgments and risk preferences of decision makers and stakeholders. Minimizando el Costo de Mantener Opciones Abiertas para la Conservación en un Clima Cambiante

Predicting species distributions for conservation decisions - Antoine Guisan; Reid Tingley; John B. Baumgartner; Ilona Naujokaitis‐Lewis; Patricia R. Sutcliffe; Ayesha I. T. Tulloch; Tracey J. Regan; Lluis Brotons; Eve McDonald‐Madden; Chrystal Mantyka‐Pringle; Tara G. Martin; Jonathan R. Rhodes; et al. (Ecology Letters, 2013)
Species distribution models (SDMs) are increasingly proposed to support conservation decision making. However, evidence of SDMs supporting solutions for on‐ground conservation problems is still scarce in the scientific literature. Here, we show that successful examples exist but are still largely hidden in the grey literature, and thus less accessible for analysis and learning. Furthermore, the decision framework within which SDMs are used is rarely made explicit. Using case studies from biological invasions, identification of critical habitats, reserve selection and translocation of endangered species, we propose that SDMs may be tailored to suit a range of decision‐making contexts when used within a structured and transparent decision‐making process. To construct appropriate SDMs to more effectively guide conservation actions, modellers need to better understand the decision process, and decision makers need to provide feedback to modellers regarding the actual use of SDMs to support conservation decisions. This could be facilitated by individuals or institutions playing the role of ‘translators’ between modellers and decision makers. We encourage species distribution modellers to get involved in real decision‐making processes that will benefit from their technical input; this strategy has the potential to better bridge theory and practice, and contribute to improve both scientific knowledge and conservation outcomes.

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

Accounting for Complementarity to Maximize Monitoring Power for Species Management - AYESHA I. T. TULLOCH; IADINE CHADÈS; HUGH P. POSSINGHAM (Conservation Biology, 2013)
To choose among conservation actions that may benefit many species, managers need to monitor the consequences of those actions. Decisions about which species to monitor from a suite of different species being managed are hindered by natural variability in populations and uncertainty in several factors: the ability of the monitoring to detect a change, the likelihood of the management action being successful for a species, and how representative species are of one another. However, the literature provides little guidance about how to account for these uncertainties when deciding which species to monitor to determine whether the management actions are delivering outcomes. We devised an approach that applies decision science and selects the best complementary suite of species to monitor to meet specific conservation objectives. We created an index for indicator selection that accounts for the likelihood of successfully detecting a real trend due to a management action and whether that signal provides information about other species. We illustrated the benefit of our approach by analyzing a monitoring program for invasive predator management aimed at recovering 14 native Australian mammals of conservation concern. Our method selected the species that provided more monitoring power at lower cost relative to the current strategy and traditional approaches that consider only a subset of the important considerations. Our benefit function accounted for natural variability in species growth rates, uncertainty in the responses of species to the prescribed action, and how well species represent others. Monitoring programs that ignore uncertainty, likelihood of detecting change, and complementarity between species will be more costly and less efficient and may waste funding that could otherwise be used for management. Contabilización de la Complementariedad para Maximizar el Poder de Monitoreo para el Manejo de Especies

Contribution of Systematic Reviews to Management Decisions - CARLY N. COOK; HUGH P. POSSINGHAM; RICHARD A. FULLER (Conservation Biology, 2013)
Systematic reviews comprehensively summarize evidence about the effectiveness of conservation interventions. We investigated the contribution to management decisions made by this growing body of literature. We identified 43 systematic reviews of conservation evidence, 23 of which drew some concrete conclusions relevant to management. Most reviews addressed conservation interventions relevant to policy decisions; only 35% considered practical on‐the‐ground management interventions. The majority of reviews covered only a small fraction of the geographic and taxonomic breadth they aimed to address (median = 13% of relevant countries and 16% of relevant taxa). The likelihood that reviews contained at least some implications for management tended to increase as geographic coverage increased and to decline as taxonomic breadth increased. These results suggest the breadth of a systematic review requires careful consideration. Reviews identified a mean of 312 relevant primary studies but excluded 88% of these because of deficiencies in design or a failure to meet other inclusion criteria. Reviews summarized on average 284 data sets and 112 years of research activity, yet the likelihood that their results had at least some implications for management did not increase as the amount of primary research summarized increased. In some cases, conclusions were elusive despite the inclusion of hundreds of data sets and years of cumulative research activity. Systematic reviews are an important part of the conservation decision making tool kit, although we believe the benefits of systematic reviews could be significantly enhanced by increasing the number of reviews focused on questions of direct relevance to on‐the‐ground managers; defining a more focused geographic and taxonomic breadth that better reflects available data; including a broader range of evidence types; and appraising the cost‐effectiveness of interventions. Contribuciones de las Revisiones Sistemáticas a las Decisiones de Manejo

Achieving Conservation Science that Bridges the Knowledge–Action Boundary - CARLY N. COOK; MICHAEL B. MASCIA; MARK W. SCHWARTZ; HUGH P. POSSINGHAM; RICHARD A. FULLER (Conservation Biology, 2013)
There are many barriers to using science to inform conservation policy and practice. Conservation scientists wishing to produce management‐relevant science must balance this goal with the imperative of demonstrating novelty and rigor in their science. Decision makers seeking to make evidence‐based decisions must balance a desire for knowledge with the need to act despite uncertainty. Generating science that will effectively inform management decisions requires that the production of information (the components of knowledge) be salient (relevant and timely), credible (authoritative, believable, and trusted), and legitimate (developed via a process that considers the values and perspectives of all relevant actors) in the eyes of both researchers and decision makers. We perceive 3 key challenges for those hoping to generate conservation science that achieves all 3 of these information characteristics. First, scientific and management audiences can have contrasting perceptions about the salience of research. Second, the pursuit of scientific credibility can come at the cost of salience and legitimacy in the eyes of decision makers, and, third, different actors can have conflicting views about what constitutes legitimate information. We highlight 4 institutional frameworks that can facilitate science that will inform management: boundary organizations (environmental organizations that span the boundary between science and management), research scientists embedded in resource management agencies, formal links between decision makers and scientists at research‐focused institutions, and training programs for conservation professionals. Although these are not the only approaches to generating boundary‐spanning science, nor are they mutually exclusive, they provide mechanisms for promoting communication, translation, and mediation across the knowledge–action boundary. We believe that despite the challenges, conservation science should strive to be a boundary science, which both advances scientific understanding and contributes to decision making. Logrando que la Ciencia de la Conservación Trasponga la Frontera Conocimiento‐Acción

Six Common Mistakes in Conservation Priority Setting - EDWARD T. GAME; PETER KAREIVA; HUGH P. POSSINGHAM (Conservation Biology, 2013)
A vast number of prioritization schemes have been developed to help conservation navigate tough decisions about the allocation of finite resources. However, the application of quantitative approaches to setting priorities in conservation frequently includes mistakes that can undermine their authors’ intention to be more rigorous and scientific in the way priorities are established and resources allocated. Drawing on well‐established principles of decision science, we highlight 6 mistakes commonly associated with setting priorities for conservation: not acknowledging conservation plans are prioritizations; trying to solve an ill‐defined problem; not prioritizing actions; arbitrariness; hidden value judgments; and not acknowledging risk of failure. We explain these mistakes and offer a path to help conservation planners avoid making the same mistakes in future prioritizations. Seis Errores Comunes en la Definición de Prioridades de Conservación

How should we grow cities to minimize their biodiversity impacts? - Jessica R. Sushinsky; Jonathan R. Rhodes; Hugh P. Possingham; Tony K. Gill; Richard A. Fuller (Global Change Biology, 2013)
Urbanization causes severe environmental degradation and continues to increase in scale and intensity around the world, but little is known about how we should design cities to minimize their ecological impact. With a sprawling style of urban development, low intensity impact is spread across a wide area, and with a compact form of development intense impact is concentrated over a small area; it remains unclear which of these development styles has a lower overall ecological impact. Here, we compare the consequences of compact and sprawling urban growth patterns on bird distributions across the city of Brisbane, Australia. We predicted the impact on bird populations of adding 84 642 houses to the city in either a compact or sprawling design using statistical models of bird distributions. We show that urban growth of any type reduces bird distributions overall, but compact development substantially slows these reductions at the city scale. Urban‐sensitive species particularly benefited from compact development at the city scale because large green spaces were left intact, whereas the distributions of nonnative species expanded as a result of sprawling development. As well as minimizing ecological disruption, compact urban development maintains human access to public green spaces. However, backyards are smaller, which impacts opportunities for people to experience nature close to home. Our results suggest that cities built to minimize per capita ecological impact are characterized by high residential density, with large interstitial green spaces and small backyards, and that there are important trade‐offs between maintaining city‐wide species diversity and people's access to biodiversity in their own backyard.

Advancing marine conservation planning in the Mediterranean Sea - Sylvaine Giakoumi; Tessa Mazor; Simonetta Fraschetti; Salit Kark; Michelle Portman; Marta Coll; Jeroen Steenbeek; Hugh Possingham (Reviews in Fish Biology and Fisheries, 2012)

Exotic species richness and native species endemism increase the impact of exotic species on islands - Jessica C. Walsh; Oscar Venter; James E. M. Watson; Richard A. Fuller; Tim M. Blackburn; Hugh P. Possingham (Global Ecology and Biogeography, 2012)
Aim Exotic species pose one of the most significant threats to biodiversity, especially on islands. The impacts of exotic species vary in severity among islands, yet little is known about what makes some islands more susceptible than others. Here we determine which characteristics of an island influence how severely exotic species affect its native biota. Location We studied 65 islands and archipelagos from around the world, ranging from latitude 65° N to 54° S. Methods We compiled a global database of 10 island characteristics for 65 islands and determined the relative importance of each characteristic in predicting the impact of exotic species using multivariate modelling and hierarchical partitioning. We defined the impact of exotic species as the number of bird, amphibian and mammal (BAM) species listed by the International Union for Conservation of Nature (IUCN) as threatened by exotics, relative to the total number of BAM species on that island. Results We found that the impact of exotic species is more severe on islands with more exotic species and a greater proportion of native species that are endemic. Unexpectedly, the level of anthropogenic disturbance did not influence an island's susceptibility to the impacts of exotic species. Main conclusions By coupling our results with studies on the introduction and establishment of exotic species, we conclude that colonization pressure, or invasion opportunities, influences all stages of the invasion process. However, species endemism, the other important factor determining the impact of exotic species, is not known to contribute to introduction and establishment success on islands. This demonstrates that different factors correlate with the initial stages of the invasion process and the subsequent impacts of those invaders, highlighting the importance of studying the impacts of exotic species directly. Our study helps identify islands that are at risk of impact by exotics and where investment should focus on preventing further invasions.

Cost-benefit analysis for intentional plant introductions under uncertainty - Hiroyuki Yokomizo; Hugh P. Possingham; Philip E. Hulme; Anthony C. Grice; Yvonne M. Buckley (Biological Invasions, 2012)

Changes in seed dispersal processes and the potential for between‐patch connectivity for an arid land daisy - Louise M. Emmerson; José M. Facelli; Peter Chesson; Hugh Possingham; Jemery R. Day (Ecology, 2012)
Dispersal is a major and critical process in population biology that has been particularly challenging to study. Animals can have major roles in seed dispersal even in species that do not appear specifically adapted to animal‐aided dispersal. This can occur by two processes: direct movement of diaspores by animals and modification of landscape characteristics by animals in ways that greatly influence dispersal. We exploited the production of large, persistent dispersal structures (seed heads, henceforth) by Erodiophyllum elderi (Asteraceae), a daisy from arid Australia, to further understand secondary dispersal. Seed head dispersal on and off animal tracks in eight E. elderi patches was monitored for 9.5 months by periodically recording the location of marked seed heads. Sites were located inside a reserve that excludes sheep but not kangaroos, and in a nearby area with both kangaroos and sheep. The distance moved and likelihood of seed head movement was higher in areas with sheep, and especially along animal tracks. There was clear evidence that seed heads were channeled down animal tracks during large rainfall events. Seed head dispersal away from patches occurred to a limited extent via their physical contact with sheep and potentially via wind dispersal. Thus, the advantages of this study system allowed us to demonstrate the two postulated effects of herbivores on dispersal via direct movement of seed heads, and two distinct indirect effects through landscape modification by herbivores from the creation of animal tracks and the denudation of vegetation.

When should we save the most endangered species? - Howard B. Wilson; Liana N Joseph; Alana L. Moore; Hugh P. Possingham (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 886–890 Abstract At the heart of our efforts to protect threatened species, there is a controversial debate about whether to give priority to cost‐effective actions or whether focusing solely on the most endangered species will ultimately lead to preservation of the greatest number of species. By framing this debate within a decision‐analytic framework, we show that allocating resources solely to the most endangered species will typically not minimise the number of extinctions in the long‐term, as this does not account for the risk of less endangered species going extinct in the future. It is only favoured when our planning timeframe is short or we have a long‐term view and we are optimistic about future conditions. Conservation funding tends to be short‐term in nature, which biases allocations to more endangered species. Our work highlights the need to consider resource allocation for biodiversity over the long‐term; ‘preventive conservation’, rather than just short‐term fire‐fighting.

Variability in Population Abundance and the Classification of Extinction Risk - HOWARD B. WILSON; BRUCE E. KENDALL; HUGH P. POSSINGHAM (Conservation Biology, 2011)
Classifying species according to their risk of extinction is a common practice and underpins much conservation activity. The reliability of such classifications rests on the accuracy of threat categorizations, but very little is known about the magnitude and types of errors that might be expected. The process of risk classification involves combining information from many sources, and understanding the quality of each source is critical to evaluating the overall status of the species. One common criterion used to classify extinction risk is a decline in abundance. Because abundance is a direct measure of conservation status, counts of individuals are generally the preferred method of evaluating whether populations are declining. Using the thresholds from criterion A of the International Union for Conservation of Nature (IUCN) Red List (critically endangered, decline in abundance of >80% over 10 years or 3 generations; endangered, decline in abundance of 50–80%; vulnerable, decline in abundance of 30–50%; least concern or near threatened, decline in abundance of 0–30%), we assessed 3 methods used to detect declines solely from estimates of abundance: use of just 2 estimates of abundance; use of linear regression on a time series of abundance; and use of state‐space models on a time series of abundance. We generated simulation data from empirical estimates of the typical variability in abundance and assessed the 3 methods for classification errors. The estimates of the proportion of falsely detected declines for linear regression and the state‐space models were low (maximum 3–14%), but 33–75% of small declines (30–50% over 15 years) were not detected. Ignoring uncertainty in estimates of abundance (with just 2 estimates of abundance) allowed more power to detect small declines (95%), but there was a high percentage (50%) of false detections. For all 3 methods, the proportion of declines estimated to be >80% was higher than the true proportion. Use of abundance data to detect species at risk of extinction may either fail to detect initial declines in abundance or have a high error rate.

Analyzing Variability and the Rate of Decline of Migratory Shorebirds in Moreton Bay, Australia - HOWARD B. WILSON; BRUCE E. KENDALL; RICHARD A. FULLER; DAVID A. MILTON; HUGH P. POSSINGHAM (Conservation Biology, 2011)
Estimating the abundance of migratory species is difficult because sources of variability differ substantially among species and populations. Recently developed state‐space models address this variability issue by directly modeling both environmental and measurement error, although their efficacy in detecting declines is relatively untested for empirical data. We applied state‐space modeling, generalized least squares (with autoregression error structure), and standard linear regression to data on abundance of wetland birds (shorebirds and terns) at Moreton Bay in southeast Queensland, Australia. There are internationally significant numbers of 8 species of waterbirds in the bay, and it is a major terminus of the large East Asian‐Australasian Flyway. In our analyses, we considered 22 migrant and 8 resident species. State‐space models identified abundances of 7 species of migrants as significantly declining and abundance of one species as significantly increasing. Declines in migrant abundance over 15 years were 43–79%. Generalized least squares with an autoregressive error structure showed abundance changes in 11 species, and standard linear regression showed abundance changes in 15 species. The higher power of the regression models meant they detected more declines, but they also were associated with a higher rate of false detections. If the declines in Moreton Bay are consistent with trends from other sites across the flyway as a whole, then a large number of species are in significant decline.

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

What works for threatened species recovery? An empirical evaluation for Australia - Martin F. J. Taylor; Paul S. Sattler; Megan Evans; Richard A. Fuller; James E. M. Watson; Hugh P. Possingham (Biodiversity and Conservation, 2011)

The Capacity of Australia's Protected‐Area System to Represent Threatened Species - JAMES E.M. WATSON; MEGAN C. EVANS; JOSIE CARWARDINE; RICHARD A. FULLER; LIANA N. JOSEPH; DAN B. SEGAN; MARTIN F.J. TAYLOR; R.J. FENSHAM; HUGH P. POSSINGHAM (Conservation Biology, 2011)
The acquisition or designation of new protected areas is usually based on criteria for representation of different ecosystems or land‐cover classes , and it is unclear how well ‐ threatened species are conserved within protected‐area networks . Here , we assessed how Australia's terrestrial protected‐area system (89 million ha , 11 . 6% of the continent) overlaps with the geographic distributions of threatened species and compared this overlap against a model that randomly placed protected areas across the continent and a spatially efficient model that placed protected areas across the continent to maximize threatened species’ representation within the protected‐area estate . We defined the minimum area needed to conserve each species on the basis of the species’ range size . We found that although the current configuration of protected areas met targets for representation of a given percentage of species’ ranges better than a random selection of areas , 166 (12 . 6%) threatened species occurred entirely outside protected areas and target levels of protection were met for only 259 (19 . 6%) species . Critically endangered species were among those with the least protection; 12 (21 . 1%) species occurred entirely outside protected areas . Reptiles and plants were the most poorly represented taxonomic groups , and amphibians the best represented . Spatial prioritization analyses revealed that an efficient protected‐area system of the same size as the current protected‐area system (11 . 6% of the area of Australia) could meet representation targets for 1272 (93 . 3%) threatened species . Moreover , the results of these prioritization analyses showed that by protecting 17 . 8% of Australia , all threatened species could reach target levels of representation , assuming all current protected areas are retained . Although this amount of area theoretically could be protected , existing land uses and the finite resources available for conservation mean land acquisition may not be possible or even effective for the recovery of threatened species . The optimal use of resources must balance acquisition of new protected areas , where processes that threaten native species are mitigated by the change in ownership or on‐ground management jurisdiction , and management of threatened species inside and outside the existing protected‐area system .

Using Conservation Evidence to Guide Management - DANIEL B. SEGAN; MADELEINE C. BOTTRILL; PETER W. J. BAXTER; HUGH P. POSSINGHAM (Conservation Biology, 2011)

From climate change predictions to actions – conserving vulnerable animal groups in hotspots at a regional scale - SÍLVIA B. CARVALHO; JOSÉ C. BRITO; EDUARDO J. CRESPO; HUGH P. POSSINGHAM (Global Change Biology, 2010)
Current climate change is a major threat to biodiversity. Species unable to adapt or move will face local or global extinction and this is more likely to happen to species with narrow climatic and habitat requirements and limited dispersal abilities, such as amphibians and reptiles. Biodiversity losses are likely to be greatest in global biodiversity hotspots where climate change is fast, such as the Iberian Peninsula. Here we assess the impact of climate change on 37 endemic and nearly endemic herptiles of the Iberian Peninsula by predicting species distributions for three different times into the future (2020, 2050 and 2080) using an ensemble of bioclimatic models and different combinations of species dispersal ability, emission levels and global circulation models. Our results show that species with Atlantic affinities that occur mainly in the North‐western Iberian Peninsula have severely reduced future distributions. Up to 13 species may lose their entire potential distribution by 2080. Furthermore, our analysis indicates that the most critical period for the majority of these species will be the next decade. While there is considerable variability between the scenarios, we believe that our results provide a robust relative evaluation of climate change impacts among different species. Future evaluation of the vulnerability of individual species to climate change should account for their adaptive capacity to climate change, including factors such as physiological climate tolerance, geographical range size, local abundance, life cycle, behavioural and phenological adaptability, evolutionary potential and dispersal ability.

Conservation Planning when Costs Are Uncertain - JOSIE CARWARDINE; KERRIE A. WILSON; STEFAN A. HAJKOWICZ; ROBERT J. SMITH; CARISSA J. KLEIN; MATT WATTS; HUGH P. POSSINGHAM (Conservation Biology, 2010)
Spatially explicit information on the financial costs of conservation actions can improve the ability of conservation planning to achieve ecological and economic objectives, but the magnitude of this improvement may depend on the accuracy of the cost estimates . Data on costs of conservation actions are inherently uncertain . For example, the cost of purchasing a property for addition to a protected‐area network depends on the individual landholder's preferences, values, and aspirations, all of which vary in space and time, and the effect of this uncertainty on the conservation priority of a site is relatively untested . We investigated the sensitivity of the conservation priority of sites to uncertainty in cost estimates . We explored scenarios for expanding (four‐fold) the protected‐area network in Queensland, Australia to represent a range of vegetation types, species, and abiotic environments, while minimizing the cost of purchasing new properties . We estimated property costs for 17, 790 10 × 10 km sites with data on unimproved land values . We systematically changed property costs and noted how these changes affected conservation priority of a site . The sensitivity of the priority of a site to changes in cost data was largely dependent on a site's importance for meeting conservation targets . Sites that were essential or unimportant for meeting targets maintained high or low priorities, respectively, regardless of cost estimates . Sites of intermediate conservation priority were sensitive to property costs and represented the best option for efficiency gains, especially if they could be purchased at a lower price than anticipated . Thus, uncertainty in cost estimates did not impede the use of cost data in conservation planning, and information on the sensitivity of the conservation priority of a site to estimates of the price of land can be used to inform strategic conservation planning before the actual price of the land is known .

Resource allocation for efficient environmental management - Michael A. McCarthy; Colin J. Thompson; Cindy Hauser; Mark A. Burgman; Hugh P. Possingham; Melinda L. Moir; Thanawat Tiensin; Marius Gilbert (Ecology Letters, 2010)
Ecology Letters (2010) Abstract Environmental managers must decide how to invest available resources. Researchers have previously determined how to allocate conservation resources among regions, design nature reserves, allocate funding to species conservation programs, design biodiversity surveys and monitoring programs, manage species and invest in greenhouse gas mitigation schemes. However, these issues have not been addressed with a unified theory. Furthermore, uncertainty is prevalent in environmental management, and needs to be considered to manage risks. We present a theory for optimal environmental management, synthesizing previous approaches to the topic and incorporating uncertainty. We show that the theory solves a diverse range of important problems of resource allocation, including distributing conservation resources among the world’s biodiversity hotspots; surveillance to detect the highly pathogenic avian influenza H5N1 virus in Thailand; and choosing survey methods for the insect order Hemiptera. Environmental management decisions are similar to decisions about financial investments, with trade‐offs between risk and reward.

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

Graph theoretic topology of the Great but small Barrier Reef world - Stuart J. Kininmonth; Glenn De’ath; Hugh P. Possingham (Theoretical Ecology, 2010)

Influence of a Threatened‐Species Focus on Conservation Planning - SIMON P. DRUMMOND; KERRIE A. WILSON; ERIK MEIJAARD; MATTHEW WATTS; RONA DENNIS; LENNY CHRISTY; HUGH P. POSSINGHAM (Conservation Biology, 2010)
Conservation efforts at local, regional, and global scales often focus on threatened species despite recent calls to adopt more equitable and potentially more economically rational approaches. Critics contend that conservation planning centered only on threatened species fails to deliver cost‐efficient conservation outcomes. We explored how planning to preserve threatened mammal species would influence the efficiency and effectiveness of conservation investments in East Kalimantan, Indonesia. We found that the explicit protection of threatened species delivered cost‐efficient outcomes in this situation, afforded adequate protection to over 90% of those species not yet considered endangered, and contributed to the partial protection of the remainder. We used Marxan, a conservation planning tool, to determine the frequency that planning units are selected in efficient reserve systems and assessed the relative risk of deforestation of each planning unit. Our methods allowed us to identify areas of the region that require the most urgent conservation action.

Avoiding Unintended Outcomes from REDD - Oscar Venter; James E.M. Watson; Erik Meijaard; William F. Laurance; Hugh P. Possingham (Conservation Biology, 2010)

A systematic evaluation of the conservation plans for the pantanal wetland in Brazil - Reinaldo Lourival; Hamish McCallum; Gordon Grigg; Claudia Arcangelo; Ricardo Machado; Hugh Possingham (Wetlands, 2009)

Dynamic marine protected areas can improve the resilience of coral reef systems - Edward T. Game; Michael Bode; Eve McDonald‐Madden; Hedley S. Grantham; Hugh P. Possingham (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1336–1346 Abstract Marine Protected Areas are usually static, permanently closed areas. There are, however, both social and ecological reasons to adopt dynamic closures, where reserves move through time. Using a general theoretical framework, we investigate whether dynamic closures can improve the mean biomass of herbivorous fishes on reef systems, thereby enhancing resilience to undesirable phase‐shifts. At current levels of reservation (10–30%), moving protection between all reefs in a system is unlikely to improve herbivore biomass, but can lead to a more even distribution of biomass. However, if protected areas are rotated among an appropriate subset of the entire reef system (e.g. rotating 10 protected areas between only 20 reefs in a 100 reef system), dynamic closures always lead to increased mean herbivore biomass. The management strategy that will achieve the highest mean herbivore biomass depends on both the trajectories and rates of population recovery and decline. Given the current large‐scale threats to coral reefs, the ability of dynamic marine protected areas to achieve conservation goals deserves more attention.

Changing perspectives on the biogeography of the tropical South Pacific: influences of dispersal, vicariance and extinction - Gunnar Keppel; Andrew J. Lowe; Hugh P. Possingham (Journal of Biogeography, 2009)
Aim The biogeographical patterns and drivers of diversity on oceanic islands in the tropical South Pacific (TSP) are synthesized. We use published studies to determine present patterns of diversity on TSP islands, the likely sources of the biota on these islands and how the islands were colonized. We also investigate the effect of extinctions. Location We focus on oceanic islands in the TSP. Methods We review available literature and published molecular studies. Results Examples of typical island features (e.g. gigantism, flightlessness, gender dimorphism) are common, as are adaptive radiations. Diversity decreases with increasing isolation from mainland sources and with decreasing size and age of archipelagos, corresponding well with island biogeographical expectations. Molecular studies support New Guinea/Malesia, New Caledonia and Australia as major source areas for the Pacific biota. Numerous studies support dispersal‐based scenarios, either over several 100 km (long‐distance dispersal) or over shorter distances by island‐hopping (stepping stones) and transport by human means (hitch‐hiking). Only one vicariance explanation, the eastward drift of continental fragments (shuttles) that may have contributed biota to Fiji from New Caledonia, is supported by some geological evidence, although there is no evidence for the transport of taxa on shuttle fragments. Another vicariance explanation, the existence of a major continental landmass in the Pacific within the last 100 Myr (Atlantis theory), receives little support and appears unlikely. Extinction of lineages in source areas and persistence in the TSP has probably occurred many times and has resulted in misinterpretation of biogeographical data. Main conclusions Malesia has long been considered the major source region for the biota of oceanic islands in the TSP because of shared taxa and high species diversity. However, recent molecular studies have produced compelling support for New Caledonia and Australia as alternative important source areas. They also show dispersal events, and not vicariance, to have been the major contributors to the current biota of the TSP. Past extinction events can obscure interpretations of diversity patterns.

Delaying conservation actions for improved knowledge: how long should we wait? - Hedley S. Grantham; Kerrie A. Wilson; Atte Moilanen; Tony Rebelo; Hugh P. Possingham (Ecology Letters, 2009)
Decisions about where conservation actions are implemented are based on incomplete knowledge about biodiversity. The Protea Atlas is a comprehensive database, containing information collated over a decade. Using this data set in a series of retrospective simulations, we compared the outcome from different scenarios of information gain, and habitat protection and loss, over a 20‐year period. We assumed that there was no information on proteas at the beginning of the simulation but knowledge improved each year. Our aim was to find out how much time we should spend collecting data before protecting habitat when there is ongoing loss of habitat. We found that, in this case, surveying for more than 2 years rarely increased the effectiveness of conservation decisions in terms of representation of proteas in protected areas and retention within the landscape. If the delay is too long, it can sometimes be more effective just using a readily available habitat map. These results reveal the opportunity costs of delaying conservation action to improve knowledge.

Optimal Allocation of Resources among Threatened Species: a Project Prioritization Protocol - LIANA N. JOSEPH; RICHARD F. MALONEY; HUGH P. POSSINGHAM (Conservation Biology, 2009)
Conservation funds are grossly inadequate to address the plight of threatened species. Government and conservation organizations faced with the task of conserving threatened species desperately need simple strategies for allocating limited resources. The academic literature dedicated to systematic priority setting usually recommends ranking species on several criteria, including level of endangerment and metrics of species value such as evolutionary distinctiveness, ecological importance, and social significance. These approaches ignore 2 crucial factors: the cost of management and the likelihood that the management will succeed. These oversights will result in misallocation of scarce conservation resources and possibly unnecessary losses. We devised a project prioritization protocol (PPP) to optimize resource allocation among New Zealand's threatened‐species projects, where costs, benefits (including species values), and the likelihood of management success were considered simultaneously. We compared the number of species managed and the expected benefits gained with 5 prioritization criteria: PPP with weightings based on species value; PPP with species weighted equally; management costs; species value; and threat status. We found that the rational use of cost and success information substantially increased the number of species managed, and prioritizing management projects according to species value or threat status in isolation was inefficient and resulted in fewer species managed. In addition, we found a clear trade‐off between funding management of a greater number of the most cost‐efficient and least risky projects and funding fewer projects to manage the species of higher value. Specifically, 11 of 32 species projects could be funded if projects were weighted by species value compared with 16 projects if projects were not weighted. This highlights the value of a transparent decision‐making process, which enables a careful consideration of trade‐offs. The use of PPP can substantially improve conservation outcomes for threatened species by increasing efficiency and ensuring transparency of management decisions.

Diversity in Current Ecological Thinking: Implications for Environmental Management - Susan A. Moore; Tabatha J. Wallington; Richard J. Hobbs; Paul R. Ehrlich; C. S. Holling; Simon Levin; David Lindenmayer; Claudia Pahl-Wostl; Hugh Possingham; Monica G. Turner; Mark Westoby (Environmental Management, 2009)

Should We Protect the Strong or the Weak? Risk, Resilience, and the Selection of Marine Protected Areas - EDWARD T. GAME; EVE McDONALD‐MADDEN; MARJI L. PUOTINEN; HUGH P. POSSINGHAM (Conservation Biology, 2008)
It is thought that recovery of marine habitats from uncontrollable disturbance may be faster in marine reserves than in unprotected habitats. But which marine habitats should be protected, those areas at greatest risk or those at least risk? We first defined this problem mathematically for 2 alternate conservation objectives. We then analytically solved this problem for both objectives and determined under which conditions each of the different protection strategies was optimal. If the conservation objective was to maximize the chance of having at least 1 healthy site, then the best strategy was protection of the site at lowest risk. On the other hand, if the goal was to maximize the expected number of healthy sites, the optimal strategy was more complex. If protected sites were likely to spend a significant amount of time in a degraded state, then it was best to protect low‐risk sites. Alternatively, if most areas were generally healthy then, counterintuitively, it was best to protect sites at higher risk. We applied these strategies to a situation of cyclone disturbance of coral reefs on Australia's Great Barrier Reef. With regard to the risk of cyclone disturbance, the optimal reef to protect differed dramatically, depending on the expected speed of reef recovery of both protected and unprotected reefs. An adequate consideration of risk is fundamental to all conservation actions and can indicate surprising routes to conservation success.

The need for speed: informed land acquisitions for conservation in a dynamic property market - Eve McDonald‐Madden; Michael Bode; Edward T. Game; Hedley Grantham; Hugh P. Possingham (Ecology Letters, 2008)
Land acquisition is a common approach to biodiversity conservation but is typically subject to property availability on the public market. Consequently, conservation plans are often unable to be implemented as intended. When properties come on the market, conservation agencies must make a choice: purchase immediately, often without a detailed knowledge of its biodiversity value; survey the parcel and accept the risk that it may be removed from the market during this process; or not purchase and hope a better parcel comes on the market at a later date. We describe both an optimal method, using stochastic dynamic programming, and a simple rule of thumb for making such decisions. The solutions to this problem illustrate how optimal conservation is necessarily dynamic and requires explicit consideration of both the time period allowed for implementation and the availability of properties.

Subpopulation Triage: How to Allocate Conservation Effort among Populations - EVE McDONALD‐MADDEN; PETER W.J. BAXTER; HUGH P. POSSINGHAM (Conservation Biology, 2008)
Threatened species often exist in a small number of isolated subpopulations. Given limitations on conservation spending, managers must choose from strategies that range from managing just one subpopulation and risking all other subpopulations to managing all subpopulations equally and poorly, thereby risking the loss of all subpopulations. We took an economic approach to this problem in an effort to discover a simple rule of thumb for optimally allocating conservation effort among subpopulations. This rule was derived by maximizing the expected number of extant subpopulations remaining given n subpopulations are actually managed. We also derived a spatiotemporally optimized strategy through stochastic dynamic programming. The rule of thumb suggested that more subpopulations should be managed if the budget increases or if the cost of reducing local extinction probabilities decreases. The rule performed well against the exact optimal strategy that was the result of the stochastic dynamic program and much better than other simple strategies (e.g., always manage one extant subpopulation or half of the remaining subpopulation). We applied our approach to the allocation of funds in 2 contrasting case studies: reduction of poaching of Sumatran tigers ( Panthera tigris sumatrae ) and habitat acquisition for San Joaquin kit foxes ( Vulpes macrotis mutica ). For our estimated annual budget for Sumatran tiger management, the mean time to extinction was about 32 years. For our estimated annual management budget for kit foxes in the San Joaquin Valley, the mean time to extinction was approximately 24 years. Our framework allows managers to deal with the important question of how to allocate scarce conservation resources among subpopulations of any threatened species.

Cost‐Effective Suppression and Eradication of Invasive Predators - PETER W. J. BAXTER; JOHN L. SABO; CHRIS WILCOX; MICHAEL A. McCARTHY; HUGH P. POSSINGHAM (Conservation Biology, 2008)
Introduced predators can have pronounced effects on naïve prey species; thus, predator control is often essential for conservation of threatened native species. Complete eradication of the predator, although desirable, may be elusive in budget‐limited situations, whereas predator suppression is more feasible and may still achieve conservation goals. We used a stochastic predator–prey model based on a Lotka‐Volterra system to investigate the cost‐effectiveness of predator control to achieve prey conservation. We compared five control strategies: immediate eradication, removal of a constant number of predators (fixed‐number control), removal of a constant proportion of predators (fixed‐rate control), removal of predators that exceed a predetermined threshold (upper‐trigger harvest), and removal of predators whenever their population falls below a lower predetermined threshold (lower‐trigger harvest). We looked at the performance of these strategies when managers could always remove the full number of predators targeted by each strategy, subject to budget availability. Under this assumption immediate eradication reduced the threat to the prey population the most. We then examined the effect of reduced management success in meeting removal targets, assuming removal is more difficult at low predator densities. In this case there was a pronounced reduction in performance of the immediate eradication, fixed‐number, and lower‐trigger strategies. Although immediate eradication still yielded the highest expected minimum prey population size, upper‐trigger harvest yielded the lowest probability of prey extinction and the greatest return on investment (as measured by improvement in expected minimum population size per amount spent). Upper‐trigger harvest was relatively successful because it operated when predator density was highest, which is when predator removal targets can be more easily met and the effect of predators on the prey is most damaging. This suggests that controlling predators only when they are most abundant is the “best” strategy when financial resources are limited and eradication is unlikely.

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Effectiveness of Surrogate Taxa in the Design of Coral Reef Reserve Systems in the Indo‐Pacific - MARIA BEGER; SHEILA A. McKENNA; HUGH P POSSINGHAM (Conservation Biology, 2007)
Implementing systematically designed reserve systems is crucial to slowing the global decline of coral reef health and diversity. Yet, the paucity of spatial data for most coral reef taxa often requires conservation planners to design reserve systems based only on a subset of taxonomic groups as surrogates for all other taxa. In terrestrial systems the validity of surrogates for reserve design is established by testing for cross‐taxon congruence (similarities in spatial patterns of species richness), but this concept has rarely been examined in the marine environment. We tested the suitability of taxa as conservation representation surrogates of coral reef species richness across the Indo‐Pacific, based on species lists of fishes, corals, and mollusks from 167 sites. First, we tested the relevance of cross‐taxon congruence patterns to predict these surrogacy patterns. We determined congruence between taxonomic groups by conducting a correlation analysis of dissimilarity values between pairs of sites. We then evaluated how well each taxonomic group represented the other groups in a marine reserve system selected by a greedy reserve‐selection algorithm relative to reserve systems selected by chance. No taxonomic group we examined was a reliable surrogate for the other groups such that site selection based on that group always represented other taxa significantly better than random selection of sites. Sites selected based on hard corals represented the other taxonomic groups in a reserve system worse than randomly selected sites. Although we found high cross‐taxon congruence between fishes and corals and between corals and mollusks, for some regions cross‐taxon congruence was not always a reliable indicator of the ability of one taxonomic group to efficiently represent another in a reserve system. We concluded that in Indo‐Pacific coral reef ecosystems one can only be sure that a target taxon is efficiently represented in a reserve system when data on that taxon are used to select a reserve system.

Incorporating the Effects of Socioeconomic Uncertainty into Priority Setting for Conservation Investment - MARISSA F. McBRIDE; KERRIE A. WILSON; MICHAEL BODE; HUGH P. POSSINGHAM (Conservation Biology, 2007)
Uncertainty in the implementation and outcomes of conservation actions that is not accounted for leaves conservation plans vulnerable to potential changes in future conditions. We used a decision‐theoretic approach to investigate the effects of two types of investment uncertainty on the optimal allocation of global conservation resources for land acquisition in the Mediterranean Basin. We considered uncertainty about (1) whether investment will continue and (2) whether the acquired biodiversity assets are secure, which we termed transaction uncertainty and performance uncertainty, respectively. We also developed and tested the robustness of different rules of thumb for guiding the allocation of conservation resources when these sources of uncertainty exist. In the presence of uncertainty in future investment ability (transaction uncertainty), the optimal strategy was opportunistic, meaning the investment priority should be to act where uncertainty is highest while investment remains possible. When there was a probability that investments would fail (performance uncertainty), the optimal solution became a complex trade‐off between the immediate biodiversity benefits of acting in a region and the perceived longevity of the investment. In general, regions were prioritized for investment when they had the greatest performance certainty, even if an alternative region was highly threatened or had higher biodiversity value. The improved performance of rules of thumb when accounting for uncertainty highlights the importance of explicitly incorporating sources of investment uncertainty and evaluating potential conservation investments in the context of their likely long‐term success.

Evolutionary Responses to Climate Change - DAVID K. SKELLY; LIANA N. JOSEPH; HUGH P. POSSINGHAM; L. KEALOHA FREIDENBURG; THOMAS J. FARRUGIA; MICHAEL T. KINNISON; ANDREW P. HENDRY (Conservation Biology, 2007)

Active Adaptive Management for Conservation - MICHAEL A. McCARTHY; HUGH P. POSSINGHAM (Conservation Biology, 2007)
Active adaptive management balances the requirements of management with the need to learn about the system being managed, which leads to better decisions. It is difficult to judge the benefit of management actions that accelerate information gain, relative to the benefit of making the best management decision given what is known at the time. We present a first step in developing methods to optimize management decisions that incorporate both uncertainty and learning via adaptive management. We assumed a manager can allocate effort to discrete units (e.g., areas for revegetation or animals for reintroduction), the outcome can be measured as success or failure (e.g., the revegetation in an area is successful or the animal survives and breeds), and the manager has two possible management options from which to choose. We further assumed that there is an annual budget that may be allocated to one or both of the two options and that the manager must decide on the allocation. We used Bayesian updating of the probability of success of the two options and stochastic dynamic programming to determine the optimal strategy over a specified number of years. The costs, level of certainty about the success of the two options, and the timeframe of management all influenced the optimal allocation of the annual budget. In addition, the choice of management objective had a large influence on the optimal decision. In a case study of Merri Creek, Melbourne, Australia, we applied the approach to determining revegetation strategies. Our approach can be used to determine how best to manage ecological systems in the face of uncertainty.

How can you conserve species that haven't been found? - Hugh P. Possingham; Hedley Grantham; Carlo Rondinini (Journal of Biogeography, 2007)

The Effect of Incremental Reserve Design and Changing Reservation Goals on the Long‐Term Efficiency of Reserve Systems - ROMOLA R. STEWART; IAN R. BALL; HUGH P. POSSINGHAM (Conservation Biology, 2007)
Selecting reserve areas based on percentages, such as 10% or 12% of a bioregion, is common in conservation planning despite widespread admission that such percentages are arbitrary and likely to be inadequate for the conservation of all biodiversity. Reserve systems based on these relatively low percentage targets are likely to require expansion in the future, resulting in the assembly of reserve systems over many years (incremental reserve design). How then will incremental reserve design, such as increasing percentage targets over time, affect the long‐term efficiency of marine reserve systems? We used South Australia as a case study to investigate how changing percentage targets affects the contribution of individual planning units to efficient reserve design. Selection frequency counts provided a measure of a planning unit's conservation value. For the majority of planning units, changing targets led to a change in their conservation value indicating, for example, that planning units identified as high‐value sites at a low‐percentage conservation target may be of lesser importance when targets are increased. Despite the variability in the value of individual planning units at different targets, there was no loss in efficiency from incremental design of reserve systems based on systematic methods compared with purpose‐built reserve systems (i.e., the system is assembled in a single iteration). The exception was when incrementally designed systems were based on South Australia's existing marine reserve system—a system developed in an ad hoc method. The result was reserve systems that were less efficient, less compact, and larger in size. This suggests that systematic approaches have an important role for efficient reserve design when there is uncertainty about the target level of reservation .

Presence–Absence versus Abundance Data for Monitoring Threatened Species - LIANA N. JOSEPH; SCOTT A. FIELD; CHRIS WILCOX; HUGH P. POSSINGHAM (Conservation Biology, 2006)
Effective detection of population trend is crucial for managing threatened species. Little theory exists, however, to assist managers in choosing the most cost‐effective monitoring techniques for diagnosing trend. We present a framework for determining the optimal monitoring strategy by simulating a manager collecting data on a declining species, the Chestnut‐rumped Hylacola ( Hylacola pyrrhopygia parkeri ), to determine whether the species should be listed under the IUCN (World Conservation Union) Red List. We compared the efficiencies of two strategies for detecting trend, abundance, and presence–absence surveys, under financial constraints. One might expect the abundance surveys to be superior under all circumstances because more information is collected at each site. Nevertheless, the presence–absence data can be collected at more sites because the surveyor is not obliged to spend a fixed amount of time at each site. The optimal strategy for monitoring was very dependent on the budget available. Under some circumstances, presence–absence surveys outperformed abundance surveys for diagnosing the IUCN Red List categories cost‐effectively. Abundance surveys were best if the species was expected to be recorded more than 16 times/year; otherwise, presence–absence surveys were best. The relationship between the strategies we investigated is likely to be relevant for many comparisons of presence–absence or abundance data. Managers of any cryptic or low‐density species who hope to maximize their success of estimating trend should find an application for our results.

Tradeoffs of different types of species occurrence data for use in systematic conservation planning - Carlo Rondinini; Kerrie A. Wilson; Luigi Boitani; Hedley Grantham; Hugh P. Possingham (Ecology Letters, 2006)
Data on the occurrence of species are widely used to inform the design of reserve networks. These data contain commission errors (when a species is mistakenly thought to be present) and omission errors (when a species is mistakenly thought to be absent), and the rates of the two types of error are inversely related. Point locality data can minimize commission errors, but those obtained from museum collections are generally sparse, suffer from substantial spatial bias and contain large omission errors. Geographic ranges generate large commission errors because they assume homogenous species distributions. Predicted distribution data make explicit inferences on species occurrence and their commission and omission errors depend on model structure, on the omission of variables that determine species distribution and on data resolution. Omission errors lead to identifying networks of areas for conservation action that are smaller than required and centred on known species occurrences, thus affecting the comprehensiveness, representativeness and efficiency of selected areas. Commission errors lead to selecting areas not relevant to conservation, thus affecting the representativeness and adequacy of reserve networks. Conservation plans should include an estimation of commission and omission errors in underlying species data and explicitly use this information to influence conservation planning outcomes.

A new method for conservation planning for the persistence of multiple species - Emily Nicholson; Michael I. Westphal; Karin Frank; Wayne A. Rochester; Robert L. Pressey; David B. Lindenmayer; Hugh P. Possingham (Ecology Letters, 2006)
Although the aim of conservation planning is the persistence of biodiversity, current methods trade‐off ecological realism at a species level in favour of including multiple species and landscape features. For conservation planning to be relevant, the impact of landscape configuration on population processes and the viability of species needs to be considered. We present a novel method for selecting reserve systems that maximize persistence across multiple species, subject to a conservation budget. We use a spatially explicit metapopulation model to estimate extinction risk, a function of the ecology of the species and the amount, quality and configuration of habitat. We compare our new method with more traditional, area‐based reserve selection methods, using a ten‐species case study, and find that the expected loss of species is reduced 20‐fold. Unlike previous methods, we avoid designating arbitrary weightings between reserve size and configuration; rather, our method is based on population processes and is grounded in ecological theory.

Characterizing a tropical deforestation wave: a dynamic spatial analysis of a deforestation hotspot in the Colombian Amazon - ANDRES ETTER; CLIVE MCALPINE; STUART PHINN; DAVID PULLAR; HUGH POSSINGHAM (Global Change Biology, 2006)
Tropical deforestation is the major contemporary threat to global biodiversity, because a diminishing extent of tropical forests supports the majority of the Earth's biodiversity. Forest clearing is often spatially concentrated in regions where human land use pressures, either planned or unplanned, increase the likelihood of deforestation. However, it is not a random process, but often moves in waves originating from settled areas. We investigate the spatial dynamics of land cover change in a tropical deforestation hotspot in the Colombian Amazon. We apply a forest cover zoning approach which permitted: calculation of colonization speed; comparative spatial analysis of patterns of deforestation and regeneration; analysis of spatial patterns of mature and recently regenerated forests; and the identification of local‐level hotspots experiencing the fastest deforestation or regeneration. The colonization frontline moved at an average of 0.84 km yr −1 from 1989 to 2002, resulting in the clearing of 3400 ha yr −1 of forests beyond the 90% forest cover line. The dynamics of forest clearing varied across the colonization front according to the amount of forest in the landscape, but was spatially concentrated in well‐defined ‘local hotspots’ of deforestation and forest regeneration. Behind the deforestation front, the transformed landscape mosaic is composed of cropping and grazing lands interspersed with mature forest fragments and patches of recently regenerated forests. We discuss the implications of the patterns of forest loss and fragmentation for biodiversity conservation within a framework of dynamic conservation planning.

Ecological‐Economic Modeling for Biodiversity Management: Potential, Pitfalls, and Prospects - FRANK WÄTZOLD; MARTIN DRECHSLER; CLAIRE W. ARMSTRONG; STEFAN BAUMGÄRTNER; VOLKER GRIMM; ANDREAS HUTH; CHARLES PERRINGS; HUGH P. POSSINGHAM; JASON F. SHOGREN; ANDERS SKONHOFT; JANA VERBOOM‐VASILJEV; CHRISTIAN WISSEL (Conservation Biology, 2006)
Ecologists and economists both use models to help develop strategies for biodiversity management. The practical use of disciplinary models, however, can be limited because ecological models tend not to address the socioeconomic dimension of biodiversity management, whereas economic models tend to neglect the ecological dimension. Given these shortcomings of disciplinary models, there is a necessity to combine ecological and economic knowledge into ecological‐economic models. It is insufficient if scientists work separately in their own disciplines and combine their knowledge only when it comes to formulating management recommendations. Such an approach does not capture feedback loops between the ecological and the socioeconomic systems. Furthermore, each discipline poses the management problem in its own way and comes up with its own most appropriate solution. These disciplinary solutions, however, are likely to be so different that a combined solution considering aspects of both disciplines cannot be found. Preconditions for a successful model‐based integration of ecology and economics include (1) an in‐depth knowledge of the two disciplines, (2) the adequate identification and framing of the problem to be investigated, and (3) a common understanding between economists and ecologists of modeling and scale. To further advance ecological‐economic modeling the development of common benchmarks, quality controls, and refereeing standards for ecological‐economic models is desirable.

Sensitivity of Marine‐Reserve Design to the Spatial Resolution of Socioeconomic Data - ELIZABETH A. RICHARDSON; MICHEL J. KAISER; GARETH EDWARDS‐JONES; HUGH P. POSSINGHAM (Conservation Biology, 2006)
Socioeconomic considerations should have an important place in reserve design. Systematic reserve‐selection tools allow simultaneous optimization for ecological objectives while minimizing costs but are seldom used to incorporate socioeconomic costs in the reserve‐design process. The sensitivity of this process to biodiversity data resolution has been studied widely but the issue of socioeconomic data resolution has not previously been considered. We therefore designed marine reserves for biodiversity conservation with the constraint of minimizing commercial fishing revenue losses and investigated how economic data resolution affected the results. Incorporating coarse‐resolution economic data from official statistics generated reserves that were only marginally less costly to the fishery than those designed with no attempt to minimize economic impacts. An intensive survey yielded fine‐resolution data that, when incorporated in the design process, substantially reduced predicted fishery losses. Such an approach could help minimize fisher displacement because the least profitable grounds are selected for the reserve. Other work has shown that low‐resolution biodiversity data can lead to underestimation of the conservation value of some sites, and a risk of overlooking the most valuable areas, and we have similarly shown that low‐resolution economic data can cause underestimation of the profitability of some sites and a risk of inadvertently including these in the reserve. Detailed socioeconomic data are therefore an essential input for the design of cost‐effective reserve networks.

Optimal eradication: when to stop looking for an invasive plant - Tracey J. Regan; Michael A. McCarthy; Peter W. J. Baxter; F. Dane Panetta; Hugh P. Possingham (Ecology Letters, 2006)
The notion of being sure that you have completely eradicated an invasive species is fanciful because of imperfect detection and persistent seed banks. Eradication is commonly declared either on an ad hoc basis, on notions of seed bank longevity, or on setting arbitrary thresholds of 1% or 5% confidence that the species is not present. Rather than declaring eradication at some arbitrary level of confidence, we take an economic approach in which we stop looking when the expected costs outweigh the expected benefits. We develop theory that determines the number of years of absent surveys required to minimize the net expected cost. Given detection of a species is imperfect, the optimal stopping time is a trade‐off between the cost of continued surveying and the cost of escape and damage if eradication is declared too soon. A simple rule of thumb compares well to the exact optimal solution using stochastic dynamic programming. Application of the approach to the eradication programme of Helenium amarum reveals that the actual stopping time was a precautionary one given the ranges for each parameter.

Objectives for Multiple‐Species Conservation Planning - EMILY NICHOLSON; HUGH P. POSSINGHAM (Conservation Biology, 2006)
The first step in conservation planning is to identify objectives. Most stated objectives for conservation, such as to maximize biodiversity outcomes, are too vague to be useful within a decision‐making framework. One way to clarify the issue is to define objectives in terms of the risk of extinction for multiple species. Although the assessment of extinction risk for single species is common, few researchers have formulated an objective function that combines the extinction risks of multiple species. We sought to translate the broad goal of maximizing the viability of species into explicit objectives for use in a decision‐theoretic approach to conservation planning. We formulated several objective functions based on extinction risk across many species and illustrated the differences between these objectives with simple examples. Each objective function was the mathematical representation of an approach to conservation and emphasized different levels of threat. Our objectives included minimizing the joint probability of one or more extinctions, minimizing the expected number of extinctions, and minimizing the increase in risk of extinction from the best‐case scenario. With objective functions based on joint probabilities of extinction across species, any correlations in extinction probabilities had to be known or the resultant decisions were potentially misleading. Additive objectives, such as the expected number of extinctions, did not produce the same anomalies. We demonstrated that the choice of objective function is central to the decision‐making process because alternative objective functions can lead to a different ranking of management options. Therefore, decision makers need to think carefully in selecting and defining their conservation goals.

Accounting for Management Costs in Sensitivity Analyses of Matrix Population Models - PETER W.J. BAXTER; MICHAEL A. McCARTHY; HUGH P. POSSINGHAM; PETER W. MENKHORST; NATASHA McLEAN (Conservation Biology, 2006)
Traditional sensitivity and elasticity analyses of matrix population models have been used to inform management decisions, but they ignore the economic costs of manipulating vital rates. For example, the growth rate of a population is often most sensitive to changes in adult survival rate, but this does not mean that increasing that rate is the best option for managing the population because it may be much more expensive than other options. To explore how managers should optimize their manipulation of vital rates, we incorporated the cost of changing those rates into matrix population models. We derived analytic expressions for locations in parameter space where managers should shift between management of fecundity and survival, for the balance between fecundity and survival management at those boundaries, and for the allocation of management resources to sustain that optimal balance. For simple matrices, the optimal budget allocation can often be expressed as simple functions of vital rates and the relative costs of changing them. We applied our method to management of the Helmeted Honeyeater ( Lichenostomus melanops cassidix ; an endangered Australian bird) and the koala ( Phascolarctos cinereus ) as examples. Our method showed that cost‐efficient management of the Helmeted Honeyeater should focus on increasing fecundity via nest protection, whereas optimal koala management should focus on manipulating both fecundity and survival simultaneously. These findings are contrary to the cost‐negligent recommendations of elasticity analysis, which would suggest focusing on managing survival in both cases. A further investigation of Helmeted Honeyeater management options, based on an individual‐based model incorporating density dependence, spatial structure, and environmental stochasticity, confirmed that fecundity management was the most cost‐effective strategy. Our results demonstrate that decisions that ignore economic factors will reduce management efficiency.

Modeling Species' Distributions to Improve Conservation in Semiurban Landscapes: Koala Case Study - JONATHAN R. RHODES; THORSTEN WIEGAND; CLIVE A. MCALPINE; JOHN CALLAGHAN; DANIEL LUNNEY; MICHIALA BOWEN; HUGH P. POSSINGHAM (Conservation Biology, 2006)
Models of species' distributions are commonly used to inform landscape and conservation planning. In urban and semiurban landscapes, the distributions of species are determined by a combination of natural habitat and anthropogenic impacts. Understanding the spatial influence of these two processes is crucial for making spatially explicit decisions about conservation actions. We present a logistic regression model for the distribution of koalas ( Phascolarctos cinereus ) in a semiurban landscape in eastern Australia that explicitly separates the effect of natural habitat quality and anthropogenic impacts on koala distributions. We achieved this by comparing the predicted distributions from the model with what the predicted distributions would have been if anthropogenic variables were at their mean values. Similar approaches have relied on making predictions assuming anthropogenic variables are zero, which will be unreliable if the training data set does not include anthropogenic variables close to zero. Our approach is novel because it can be applied to landscapes where anthropogenic variables are never close to zero. Our model showed that, averaged across the study area, natural habitat was the main determinant of koala presence. At a local scale, however, anthropogenic impacts could be more important, with consequent implications for conservation planning. We demonstrated that this modeling approach, combined with the visual presentation of predictions as a map, provides important information for making decisions on how different conservation actions should be spatially allocated. This method is particularly useful for areas where wildlife and human populations exist in close proximity.

Rejoinder: uncertainty and decision making - Benjamin S. Halpern; Helen M. Regan; Hugh P. Possingham; Michael A. McCarthy (Ecology Letters, 2006)

Accounting for uncertainty in marine reserve design - Benjamin S. Halpern; Helen M. Regan; Hugh P. Possingham; Michael A. McCarthy (Ecology Letters, 2006)
Ecosystems and the species and communities within them are highly complex systems that defy predictions with any degree of certainty. Managing and conserving these systems in the face of uncertainty remains a daunting challenge, particularly with respect to developing networks of marine reserves. Here we review several modelling frameworks that explicitly acknowledge and incorporate uncertainty, and then use these methods to evaluate reserve spacing rules given increasing levels of uncertainty about larval dispersal distances. Our approach finds similar spacing rules as have been proposed elsewhere – roughly 20–200 km – but highlights several advantages provided by uncertainty modelling over more traditional approaches to developing these estimates. In particular, we argue that uncertainty modelling can allow for (1) an evaluation of the risk associated with any decision based on the assumed uncertainty; (2) a method for quantifying the costs and benefits of reducing uncertainty; and (3) a useful tool for communicating to stakeholders the challenges in managing highly uncertain systems. We also argue that incorporating rather than avoiding uncertainty will increase the chances of successfully achieving conservation and management goals.

Establishing Representative No‐Take Areas in the Great Barrier Reef: Large‐Scale Implementation of Theory on Marine Protected Areas - LEANNE FERNANDES; JON DAY; ADAM LEWIS; SUZANNE SLEGERS; BRIGID KERRIGAN; DAN BREEN; DARREN CAMERON; BELINDA JAGO; JAMES HALL; DAVE LOWE; JAMES INNES; JOHN TANZER; et al. (Conservation Biology, 2005)
The Great Barrier Reef Marine Park, an area almost the size of Japan, has a new network of no‐take areas that significantly improves the protection of biodiversity. The new marine park zoning implements, in a quantitative manner, many of the theoretical design principles discussed in the literature. For example, the new network of no‐take areas has at least 20% protection per “bioregion,” minimum levels of protection for all known habitats and special or unique features, and minimum sizes for no‐take areas of at least 10 or 20 km across at the smallest diameter. Overall, more than 33% of the Great Barrier Reef Marine Park is now in no‐take areas (previously 4.5%). The steps taken leading to this outcome were to clarify to the interested public why the existing level of protection was inadequate; detail the conservation objectives of establishing new no‐take areas; work with relevant and independent experts to define, and contribute to, the best scientific process to deliver on the objectives; describe the biodiversity (e.g., map bioregions); define operational principles needed to achieve the objectives; invite community input on all of the above; gather and layer the data gathered in round‐table discussions; report the degree of achievement of principles for various options of no‐take areas; and determine how to address negative impacts. Some of the key success factors in this case have global relevance and include focusing initial communication on the problem to be addressed; applying the precautionary principle; using independent experts; facilitating input to decision making; conducting extensive and participatory consultation; having an existing marine park that encompassed much of the ecosystem; having legislative power under federal law; developing high‐level support; ensuring agency priority and ownership; and being able to address the issue of displaced fishers.

Zero tolerance ecology: improving ecological inference by modelling the source of zero observations - Tara G. Martin; Brendan A. Wintle; Jonathan R. Rhodes; Petra M. Kuhnert; Scott A. Field; Samantha J. Low‐Choy; Andrew J. Tyre; Hugh P. Possingham (Ecology Letters, 2005)
A common feature of ecological data sets is their tendency to contain many zero values. Statistical inference based on such data are likely to be inefficient or wrong unless careful thought is given to how these zeros arose and how best to model them. In this paper, we propose a framework for understanding how zero‐inflated data sets originate and deciding how best to model them. We define and classify the different kinds of zeros that occur in ecological data and describe how they arise: either from ‘true zero’ or ‘false zero’ observations. After reviewing recent developments in modelling zero‐inflated data sets, we use practical examples to demonstrate how failing to account for the source of zero inflation can reduce our ability to detect relationships in ecological data and at worst lead to incorrect inference. The adoption of methods that explicitly model the sources of zero observations will sharpen insights and improve the robustness of ecological analyses.

Efficiency, costs and trade-offs in marine reserve system design - Romola R. Stewart; Hugh P. Possingham (Environmental Modeling & Assessment, 2005)

A theory for optimal monitoring of marine reserves - Leah R. Gerber; Maria Beger; Michael A. McCarthy; Hugh P. Possingham (Ecology Letters, 2005)
Monitoring of marine reserves has traditionally focused on the task of rejecting the null hypothesis that marine reserves have no impact on the population and community structure of harvested populations. We consider the role of monitoring of marine reserves to gain information needed for management decisions. In particular we use a decision theoretic framework to answer the question: how long should we monitor the recovery of an over‐fished stock to determine the fraction of that stock to reserve? This exposes a natural tension between the cost (in terms of time and money) of additional monitoring, and the benefit of more accurately parameterizing a population model for the stock, that in turn leads to a better decision about the optimal size for the reserve with respect to harvesting. We found that the optimal monitoring time frame is rarely more than 5 years. A higher economic discount rate decreased the optimal monitoring time frame, making the expected benefit of more certainty about parameters in the system negligible compared with the expected gain from earlier exploitation.

Measuring and Incorporating Vulnerability into Conservation Planning - Kerrie Wilson; Robert L. Pressey; Adrian Newton; Mark Burgman; Hugh Possingham; Chris Weston (Environmental Management, 2005)

Linking Wild and Captive Populations to Maximize Species Persistence: Optimal Translocation Strategies - BRIGITTE TENHUMBERG; ANDREW J. TYRE; KATRIONA SHEA; HUGH P. POSSINGHAM (Conservation Biology, 2004)
Captive breeding of animals is widely used to manage endangered species, frequently with the ambition of future reintroduction into the wild. Because this conservation measure is very expensive, we need to optimize decisions, such as when to capture wild animals or release captive‐bred individuals into the wild. It is unlikely that one particular strategy will always work best; instead, we expect the best decision to depend on the number of individuals in the wild and in captivity. We constructed a first‐order Markov‐chain population model for two populations, one captive and one wild, and we used stochastic dynamic programming to identify optimal state‐dependent strategies. The model recommends unique sequences of optimal management actions over several years. A robust rule of thumb for species that can increase faster in captivity than in the wild is to capture the entire wild population whenever the wild population is below a threshold size of 20 females. This rule applies even if the wild population is growing and under a broad range of different parameter values. Once a captive population is established, it should be maintained as a safety net and animals should be released only if the captive population is close to its carrying capacity. We illustrate the utility of this model by applying it to the Arabian oryx ( Oryx leucoryx ). The threshold for capturing the entire Arabian oryx population in the wild is 36 females, and captive‐bred individuals should not be released before the captive facilities are at least 85% full.

Minimizing the cost of environmental management decisions by optimizing statistical thresholds - Scott A. Field; Andrew J. Tyre; Niclas Jonzén; Jonathan R. Rhodes; Hugh P. Possingham (Ecology Letters, 2004)
Environmental management decisions are prone to expensive mistakes if they are triggered by hypothesis tests using the conventional Type I error rate ( α ) of 0.05. We derive optimal α ‐levels for decision‐making by minimizing a cost function that specifies the overall cost of monitoring and management. When managing an economically valuable koala population, it shows that a decision based on α = 0.05 carries an expected cost over $5 million greater than the optimal decision. For a species of such value, there is never any benefit in guarding against the spurious detection of declines and therefore management should proceed directly to recovery action. This result holds in most circumstances where the species’ value substantially exceeds its recovery costs. For species of lower economic value, we show that the conventional α ‐level of 0.05 rarely approximates the optimal decision‐making threshold. This analysis supports calls for reversing the statistical ‘burden of proof’ in environmental decision‐making when the cost of Type II errors is relatively high.

Does conservation planning matter in a dynamic and uncertain world? - Eli Meir; Sandy Andelman; Hugh P. Possingham (Ecology Letters, 2004)
Loss of biodiversity is one of the world's overriding environmental challenges. Reducing those losses by creating reserve networks is a cornerstone of global conservation and resource management. Historically, assembly of reserve networks has been ad hoc , but recently the focus has shifted to identifying optimal reserve networks. We show that while comprehensive reserve network design is best when the entire network can be implemented immediately, when conservation investments must be staged over years, such solutions actually may be sub‐optimal in the context of biodiversity loss and uncertainty. Simple decision rules, such as protecting the available site with the highest irreplaceability or with the highest species richness, may be more effective when implementation occurs over many years.

The predictive accuracy of population viability analysis: a test using data from two small mammal species in a fragmented landscape - Stephen J. Ball; David B. Lindenmayer; Hugh P. Possingham (Biodiversity and Conservation, 2003)

Reliability of Relative Predictions in Population Viability Analysis - Michael A. McCarthy; Sandy J. Andelman; Hugh P. Possingham (Conservation Biology, 2003)
Despite numerous claims that population viability analysis ( PVA ) makes reliable predictions of the relative risks of extinction, there is little evidence to support this assertion. To assess the veracity of the claim, we investigated uncertainty in the relative predictions of a PVA model with simulation experiments. We used a stochastic Ricker model to investigate the reliability of predicted changes in risks of decline in response to changes in parameters, the reliability of ranking species in terms of their relative threat, and the reliability of choosing the better of two management decisions. The predicted changes in risks of decline within 100 years were more reliable than absolute predictions. We made useful predictions of relative risks using only 10 years of data. Across 160 different parameter combinations, the rank correlation between the true risks of extinction within 100 years and predicted risks was 0.59 with 10 years of data, increasing to 0.89 with 100 years of data. We identified the better of two management strategies 67–74% of the time using 10 years of data, increasing to 92–93% of the time with 100 years of data. Our results demonstrate that, despite considerable uncertainty in the predicted risks of decline, PVA may reliably contribute to the management of threatened species.

Applying a Decision‐Theory Framework to Landscape Planning for Biodiversity: Follow‐Up to Watson et al. - Michael I. Westphal; Hugh P. Possingham (Conservation Biology, 2003)

Optimizing Habitat Protection Using Demographic Models of Population Viability - Robert G. Haight; Brian Cypher; Patrick A. Kelly; Scott Phillips; Hugh P. Possingham; Katherine Ralls; Anthony M. Starfield; P. J. White; Daniel Williams (Conservation Biology, 2002)
Expanding habitat protection is a common tactic for species conservation. When unprotected habitat is privately owned, decisions must be made about which areas to protect by land purchase or conservation easement. To address this problem, we developed an optimization framework for choosing the habitat‐protection strategy that minimizes the risk of population extinction subject to an upper bound on funding. The framework is based on the idea that an extinction‐risk function that predicts the relative effects of varying the quantity and quality of habitat can be estimated from the results of a demographic model of population viability. We used the framework to address the problem of expanding the protected habitat of a core population of the endangered San Joaquin kit fox ( Vulpes macrotis mutica ) in the Panoche area in central California. We first developed a stochastic demographic model of the kit fox population. Predictions from the simulation model were used to estimate an extinction‐risk function that depended on areas of good‐ and fair‐quality habitat. The risk function was combined with costs of habitat protection to determine cost‐efficient protection strategies and risk‐cost curves showing how extinction risk could be reduced at minimum cost for increasing levels of funding. One important result was that cost‐efficient shares of the budget used to protect different types of habitat changed as the budget increased and depended on the relative costs of available habitat and the relative effects of habitat protection on extinction risk. Another important finding was the sensitivity of the location and slope of the risk‐cost curve to assumptions about the spatial configuration of available habitat. When the location and slope of the risk‐cost curve are sensitive to model assumptions, resulting predictions of extinction risk and risk reduction per unit cost should be used very cautiously in ranking conservation options among different species or populations. The application is an example of how the results of a complex demographic model of population viability can be synthesized for use in optimization analyses to determine cost‐efficient habitat‐protection strategies and risk‐cost tradeoffs.

Mathematical Methods for Spatially Cohesive Reserve Design - Mark D. McDonnell; Hugh P. Possingham; Ian R. Ball; Elizabeth A. Cousins (Environmental Modeling & Assessment, 2002)

A Method for Setting the Size of Plant Conservation Target Areas - Mark A. Burgman; Hugh P. Possingham; A. Jasmyn J. Lynch; David A. Keith; Michael A. McCarthy; Stephen D. Hopper; Wendy L. Drury; Jason A. Passioura; Robert J. Devries (Conservation Biology, 2001)
Realistic time frames in which management decisions are made often preclude the completion of the detailed analyses necessary for conservation planning. Under these circumstances, efficient alternatives may assist in approximating the results of more thorough studies that require extensive resources and time. We outline a set of concepts and formulas that may be used in lieu of detailed population viability analyses and habitat modeling exercises to estimate the protected areas required to provide desirable conservation outcomes for a suite of threatened plant species. We used expert judgment of parameters and assessment of a population size that results in a specified quasiextinction risk based on simple dynamic models. The area required to support a population of this size is adjusted to take into account deterministic and stochastic human influences, including small‐scale disturbance, deterministic trends such as habitat loss, and changes in population density through processes such as predation and competition. We set targets for different disturbance regimes and geographic regions. We applied our methods to Banksia cuneata, Boronia keysii, and Parsonsia dorrigoensis, resulting in target areas for conservation of 1102, 733, and 1084 ha, respectively. These results provide guidance on target areas and priorities for conservation strategies.

Modelling the viability of metapopulations of the endangered Leadbeater's possum in south-eastern Australia - David B. Lindenmayer; Hugh P. Possingham (Biodiversity and Conservation, 1995)